A versatile plasmid platform for auxotrophic complementation in attenuated Mycobacterium bovis BCG - Andriele Bonemann Madruga; Jady Duarte Nogueira; Mara Andrade Colares Maia; Natasha Rodrigues de Oliveira; Maria Eduarda Ehlert; Valentina Gessinger Ferreira; Bruna Silveira Pacheco; Fabiana Kommling Seixas; Tiago Veiras Collares; Izani Bonel Acosta; Antônio Sergio Varela; Odir Antônio Dellagostin; et al. (Molecular Biology Reports, 2026)
Background Mycobacterium bovis BCG is widely used as a vaccine vector due to its safety, genetic stability, and immunomodulatory properties. However, current expression systems for BCG transformation rely on antibiotic resistance genes, raising biosafety concerns. Therefore, alternative strategies—such as the use of auxotrophic strains—are highly desirable. Our group previously employed BioBrick™ technology to construct the pUP500 plasmid series containing various mycobacterial promoters. We engineered these plasmids for the auxotrophic complementation of BCG ΔLeuD, a leucine-auxotrophic strain, using an antibiotic-free and BioBrick™-compatible approach. Methods and Results The auxotrophic complementation cassette pAN- leuD was cloned into pUP500 plasmids. Subsequently, the egfp gene was inserted downstream of the promoters, the kanamycin resistance gene was removed, and fluorescence was assessed by flow cytometry, qPCR and confocal microscopy in BCG grown in 7H9 medium and inside macrophages. Auxotrophic complementation was confirmed by growth of transformants in non-selective medium and analysis of leuD expression, and plasmid stability was evaluated along six BCG generations. Strains harboring plasmids containing the pAN and HspX promoters exhibited stronger fluorescence levels both in vitro and within macrophages. In contrast, the 18 kDa promoter demonstrated marked activation specifically in the intracellular environment, driving robust gene expression inside macrophages. These expression patterns were significantly higher compared to strains carrying the Ag85B or Hsp60 promoters, as well as to the negative control. Except for the Hsp60 construct, all plasmids exhibited robust in vitro stability across six consecutive passages, supporting their potential as reliable expression systems for heterologous antigens in therapeutic and vaccine applications. Conclusions We developed five BioBrick™-compatible plasmids with distinct promoters for auxotrophic complementation and antigen expression in BCG ΔLeuD, eliminating the need for antibiotic-based selection. This standardized plasmid series reduces vector-related variability in comparative studies and provides a diverse promoter repertoire that may enhance the stability and efficacy of recombinant BCG ΔLeuD strains, representing a valuable advancement for prophylactic and therapeutic vaccine development.

Acinetobacter venetianus AMO1502: a strain isolated from an oil spill capable of degrading diesel and producing active surface compounds - Marcelo Pereira de Oliveira; Alan Portal D’Almeida; Tiago Lima de Albuquerque; Vânia Maria Maciel Melo; Tigressa Helena Soares Rodrigues; Maria Valderez Ponte Rocha (Brazilian Journal of Microbiology, 2026)

Expanding the known distribution of Brazilian horse flies (Diptera: Tabanidae) using citizen science data - Fabíola Rodrigues Branquinho; Augusto Loureiro Henriques; Tiago Kütter Krolow (Journal of Insect Conservation, 2026)
iNaturalist has been establishing itself as a bridge between researchers and the public, providing relevant data for scientific studies while making science more accessible beyond academia. Horseflies can serve as a useful model group when using the platform to expand distribution records, due to the relative ease of identifying members of the family from photographs. The study was organized into four stages: (i) defining the initial search scope, (Tabanidae) × (Brazil/states); (ii) selecting and filtering groups; (iii) confirming identifications; and (iv) checking and comparing state-level distribution data with records from the Brazilian Taxonomic Catalog of Fauna (CTFB).A total of 159 observations were made for eight previously selected genera, of which 25 observations that represent eleven species were new records for Brazilian states: Scepsis appendiculata (BA and RS), Catachlorops potator (RS), Erioneura fuscipennis (ES), Eutabanus pictus (MT), Lepiselaga albitarsis (SC), Lepiselaga crassipes (PE and ES), Leucotabanus flavinotum (RO), Selasoma tibiale (AL, PE, PR, and RS), Stibasoma aureoguttatum (PR), Stibasoma bela (MG), and Stibasoma flaviventris (BA).In addition to these results, we highlight that the use of the iNaturalist platform makes it possible to obtain relevant information from under-sampled areas, traditionally considered knowledge gaps for the taxon, and can also reveal details of morphology, coloration of live specimens, sexual dimorphism, habitat preferences, and behavior of the observed species. Implications for insect conservation This study demonstrates the potential of citizen science to expand access to distribution data and knowledge about tabanids, while also encouraging their appreciation by naturalists, thereby contributing to the conservation of the family.

Inclusion of microalga Dunaliella salina in the diet of laying hens: effects on egg quality and sensory traits - Obete Madacussengua; Cátia Falcão Martins; Ana Beatriz Rodrigues Tavares; Daniela Filipa Pires Carvalho; Ana Rita Mendes; Tiago Guerra; António Pagarete; Suzana Ferreira-Dias; Miguel Pedro Mourato; José António Mestre Prates; André Martinho de Almeida; Madalena Lordelo (Algal Research, 2026)

Clonal Propagation of Khaya spp.: Epicormic Shoot Emission in Adult African Mahogany Species - Júlio Cézar Tannure Faria; Laura Ribeiro Atala; Cassia dos Santos Azevedo; Marcos Vinicius Winckler Caldeira; Tiago de Oliveira Godinho; Fatima Conceição Marquez Piña-Rodrigues (Forest Science, 2026)
Research on vegetative propagation in the genus Khaya remains limited and has focused mainly on juvenile trees, which restricts the selection of plus trees previously tested for growth potential and economic value. This study aimed to evaluate the vegetative propagation of three African mahogany species by inducing epicormic shoots in adult trees, and to investigate evidence of rejuvenation/reinvigoration during adventitious rooting, as well as the influence of branch diameter on bud and shoot emission. Plant material was collected from an experimental plantation using basal branches of 10-year-old trees. For each species, 72 leafless branches were standardized and maintained in a climate-controlled greenhouse. The experiment followed a completely randomized design with three diameter classes. After 21 days, the number of buds and shoots emitted per branch was recorded. Biochemical analyses included the antioxidant enzymes superoxide dismutase (SOD) and catalase (CAT), total proteins, and total carbohydrates to characterize metabolic differences between adult tissues and epicormic shoots. Results indicate that branch diameter had a significant effect on bud and shoot emission in all three African mahogany species, with branches 4.5–6 cm in diameter being the most suitable source material. For assessing tissue rejuvenation and metabolism, SOD and CAT activities in K. senegalensis , SOD activity in K. grandifoliola , and total carbohydrate content in K. ivorensis were the most responsive biochemical variables for distinguishing epicormic shoots from adult tissues. Although adventitious rooting percentages were low, this study indicates that epicormic shoot induction in adult trees is a feasible strategy for obtaining vegetative propagules.

Salicylic acid induces dose-dependent and organ-specific modulation of phenolic profiles and antioxidant activity in Polygonum maritimum L. in vitro cultures - Adeola Oyesiji; Sylwester Ślusarczyk; Adam Matkowski; Eliana Fernandes; Marie Binnert; Tiago Braga; Luísa Custódio; Maria João Rodrigues (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Defatting irradiated cricket flour to improve its functional properties and develop innovative hybrid beef patties - Guilherme Fernando Cavalcante Bruno Amaral Gama; Fernanda Beatriz Jacquiminouth Lopes; Marise Aparecida Rodrigues Pollonio; Tiago Bueno de Moraes; Carmen Josefina Contreras Castillo; Camila de Souza Paglarini (Food Chemistry, 2026)

Bridging the interoperability gap in life cycle assessment: the lavoisier conversion framework and implementation for EcoSpold 2 and ILCD formats - José Paulo Pereira das Dores Pilz Savioli; Tiago Emmanuel Nunes Braga; Thiago Oliveira Rodrigues; Silvana Aparecida Borsetti Gregorio Vidotti; Cássia Maria Lie Ugaya (The International Journal of Life Cycle Assessment, 2026)
Purpose Interoperability among Life Cycle Inventory (LCI) formats remains a persistent challenge, even for widely used standards such as EcoSpold 2 and ILCD, limiting data exchange and reuse. Converters are commonly employed to bridge these gaps, yet existing tools are mostly commercial, tied to specific software ecosystems and lack robust open-source alternatives. To address this limitation, we introduce Lavoisier, an open-source conversion framework designed to enable reliable transformation of LCI datasets across different formats. Methods Lavoisier is designed with three modules: the input, the mapping of fields (including conversion logic) and the output, all of which accept new entries for different formats in a modular way. As a case study, we implemented in Lavoisier a bidirectional conversion flow between EcoSpold 2 and ILCD. This was achieved by leveraging existing documentation and gathering understanding of the structural and semantic characteristics of both formats. The primary goal in the case study was to ensure minimal data loss while respecting the constraints and modelling principles of each format. Conversions were assessed and classified into subclasses based on type (direct, indirect, incomplete, structural and not converted) and functional relevance of data (computational data, interpretative metadata, complementary metadata and not used). Results and discussion The results show that Lavoisier successfully converts the majority of computational data and interpretative metadata between EcoSpold 2 and ILCD, with conversion results and limitations logged. Direct and indirect conversions dominate across both pathways, with most losses concentrated in elements inherently unsupported by the target format (such as EcoSpold 2’s pedigree coefficients or ILCD’s richer source and contact structures). Tests using 115 EcoSpold 2 and 116 ILCD datasets showed high accuracy in unit handling, equation translation, uncertainty processing and intermediate flow reconstruction. The largest limitations stem from format-level constraints, particularly rigid reference lists for elementary flows, units and properties, which prevented full conversion. Overall, results indicate strong conversion performance constrained only by structural differences external to Lavoisier. Conclusion Lavoisier enables a translation of LCI datasets between EcoSpold 2 and ILCD that preserves nearly all commonly used quantitative and metadata information. Additionally, logs communicate limitations in a transparent way. However, full interoperability remains limited by intrinsic format (and methodology) differences such as incompatible reference lists, missing provider fields and non-extensible metadata structures. This is a barrier that converters alone cannot overcome. Even so, Lavoisier substantially reduces manual rework and has the potential to increase data reusability.

Low electric charge loading in a sequencing batch electro-membrane bioreactor: influence of aeration intensity on treatment performance, biomass activity, and membrane fouling - Tiago José Belli; Emerson Souza; Caroline Rodrigues; André Aguiar Battistelli; Wanderli Leite; Miriam Cristina Santos Amaral; Flávio Rubens Lapolli (Environmental Science and Pollution Research, 2026)
This study investigates the performance of a sequencing batch electro-membrane bioreactor (SB-EMBR) operated under low electric charge loading (39.9 mAh L⁻ 1 ), focusing on the effects of aeration intensity on treatment performance, biomass activity, and membrane fouling. The reactor was operated at a current density of 10 A m −2 and three specific aeration demand levels (SADₘ = 0.48, 0.24, and 0.12 m 3 m⁻ 2 h⁻ 1 ). Organic matter and phosphorus removals remained consistently high (> 90% COD removal; TP < 1.0 mg L⁻ 1 ) regardless of aeration intensity. In contrast, ammonium removal efficiency declined from 99.5 to 74.7% as the SADₘ decreased from 0.48 to 0.12 m 3 m⁻ 2 h⁻ 1 . Batch assays revealed reduced activity of polyphosphate-accumulating organisms under oxygen-limited conditions. The pronounced decrease in the P-release/COD-uptake ratio from 0.172 to 0.0164 mol P mol⁻ 1 C indicates that TP removal at low dissolved oxygen became predominantly governed by chemical coagulation rather than the biological phosphorus removal process. The calculated Al/P molar ratio of 2.32 mol Al mol⁻ 1 P was sufficient to sustain phosphorus removal through both precipitation and adsorption onto aluminum hydroxides. Reduced aeration favored anoxic phosphorus uptake, increasing the denitrifying phosphate assimilation potential from 18 to 41%. The membrane fouling rate increased from 1.02 to 4.81 kPa d⁻ 1 as aeration decreased, mainly due to diminished shear forces, soluble microbial products accumulation (+ 205%), floc size reduction (− 50.1%), and higher capillary suction time (+ 123%). Owing to the short current application (1.6 h d⁻ 1 ), the additional electrocoagulation cost was only 0.07 USD m⁻ 3 , lower than values reported for continuous-flow EMBRs. Overall, operation of the SB-EMBR under reduced electric charge loading demonstrated promising energy efficiency while maintaining stable and satisfactory pollutant removal even at low aeration intensities.

Contribution of citizen science to marine biodiversity research: Divers’ participation in citizen science platforms in Portugal - Rita Rodrigues; Patrícia Tiago; Bruno Pinto (Ocean & Coastal Management, 2026)

Impacts of coastal dynamics on blue carbon ecosystems: Assessing long-term carbon balance in mangroves of Amazon coast - Vitor L.A. Rodrigues; Carla F.O. Pacheco; André Vassoler; Tiago O. Ferreira; Angelo F. Bernardino (Forest Ecology and Management, 2026)

Performance, non-carcass components, serum biochemistry panel and intestinal morphology of Texel lambs fed with bioactive peptides - Gabriella de Oliveira Nascimento; Kamila de Sousa Otávio; Josiel Ferreira; Hugo Jayme Mathias Coelhon Peron; Elis Aparecido Bento; Francisco Ribeiro de Araujo Neto; Abílio Paulo Changule; Paulla Christina Rodrigues De Oliveira; Álvaro Ferreira Santos; Ane Elizi Alves da Silva Gomes; Gabrielly Borges Coelho Santos; Larissa Souza Garcia; et al. (Tropical Animal Health and Production, 2026)

Artificial intelligence in wildland–urban interface wildfire management: a two‑phase review combining bibliometric mapping and thematic analysis - Dener Silva; Tiago Miguel Ferreira; Hugo Rodrigues (Natural Hazards, 2026)
Wildland-Urban Interface (WUI) areas are critical zones where human settlements and wildland fuels intersect, resulting in heightened wildfire risk and increased potential for losses. This study presents a two‑phase review of literature where artificial intelligence (AI) is applied in wildfire and WUI studies, combining bibliometric mapping for wildfires and a thematic content analysis for WUI. In Phase One, over 3500 publications indexed in Scopus were analysed, searching generally for AI applications in wildfire research to investigate trends. This analysis revealed four dominant clusters: deep learning around computer vision, remote sensing-driven analysis, Random Forests and ensembles with environmental variables, and decision-support prediction. For this phase, the results suggested a notable rise in machine learning after 2016, potentially driven by increased computational capacity and the availability of high-resolution remote sensing, aligned to concerns about the growing impacts of wildfires. Phase Two focused on 52 peer‑reviewed studies explicitly addressing AI for WUI contexts. They were categorised into five thematic areas: risk and vulnerability, human behaviour and decision support, vegetation and fuel, detection and monitoring, and fire behaviour and spread. Models such as random forests, convolutional neural networks, and traditional statistical integrate various datasets, including satellite and UAV/LiDAR imagery, GIS information, and topographic-climatic and socio-economic indicators. The results indicate that AI has contributed to accurate models in spatial resolution and predictive risk for WUI areas, but faces challenges such as simplified WUI maps, fragmented and scarce data, limited model generalisation, and interpretability. Overall, this review identifies opportunities for detailed and diverse WUI mapping, explainable AI, and interdisciplinary collaboration providing means for actionable strategies for WUI communities.

Systems toxicology of naturally aged polypropylene microplastics in zebrafish - Raíssa de Oliveira Ferreira; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Ariane Guimarães; Thiarlen Marinho da Luz; Guilherme Malafaia (NanoImpact, 2026)

Waste-derived biochar as filter media in a compact vertical-flow constructed wetland treating raw domestic wastewater - Eduardo Bello Rodrigues; Elisângela Edila Schneider; Tiago José Belli; Pablo Heleno Sezerino; Flávio Rubens Lapolli; Daniele Damasceno Silveira (Ecological Engineering, 2026)

Hydro-Mechanical Numerical Analysis of Fault Reactivation Considering Fault-Zone Architecture in Clastic Reservoirs - Tasso Carvalho da Silva; Igor Fernandes Gomes; Leonardo José do Nascimento Guimarães; José Antônio Barbosa; Tiago Siqueira de Miranda; Thiago Rodrigues; Tallys Celso Mineiro; Yago Ryan Pinheiro dos Santos (Geotechnical and Geological Engineering, 2026)
Geological faults are key discontinuities in sedimentary basins and strongly influence the hydraulic and mechanical behavior of hydrocarbon reservoirs. Fault zones typically contain a low-permeability core and a more permeable damage zone, generating sharp contrasts in petrophysical and mechanical properties. Stress variations from production, injection, or geological storage may induce fault reactivation, dilatancy, and permeability enhancement, yet many numerical studies still treat faults as homogeneous features. This study develops a two-dimensional coupled hydro-mechanical framework that explicitly represents fault-core and damage-zone domains incorporating viscoelastoplastic behavior through a Mohr–Coulomb model with Perzyna viscoplasticity. The novelty of this approach lies in integrating realistic geological architecture with explicit core-damage-zone contrasts and coupled viscoelastoplastic analysis under production and injection scenarios in compartmentalized reservoirs. Based on seismic interpretation of the Laurentian Basin (offshore Canada), CODE_BRIGHT simulations model single-phase flow in a deformable reservoir to evaluate stress redistribution, permeability evolution, and deformation. Sensitivity analyses indicate that an injection pressure of 6.5 MPa triggers fault reactivation, causing dilation-induced permeability increases and establishing hydraulic communication between the deep reservoir and the overlying aquifer previously sealed by Faults 01 and 02. Fault reactivation induces an asymmetric deformational field, with horizontal displacements of approximately + 25 cm along Fault 02 and − 13 cm along Fault 01, and a distortional vertical response characterized by a dip-slip response with differential block-scale subsidence and uplift, with a maximum subsidence of ~ 7 cm. Shear stresses concentrate mainly along Faults 01 and 02, particularly near their tips, indicating stress redistribution toward Fault 03. These results underscore the importance of internal fault-zone heterogeneity in controlling deformation, stress evolution, and transmissivity, with implications for CO 2 storage, geothermal systems, industrial injection, and geotechnical applications.

Corrigendum to “Microplastic pollution across the Brazilian coastline: Evidence from the MICROMar project, the largest coastal survey in the Global South” [Environ. Res. 286, Part 2, (2025) 122923] - Thiarlen Marinho da Luz; Rafaela Ribeiro de Brito; Raíssa de Oliveira Ferreira; Ariane Guimarães; Bárbara Beatriz da Silva Nunes; Aline Sueli de Lima Rodrigues; Abraão Tiago Batista Guimarães; Ítalo Nascimento Freitas; Stênio Gonçalves da Silva Matos; Élida Priscila Bogéa Carvalho; Juliana dos Santos Mendonça; Christine C. Gaylarde; et al. (Environmental Research, 2026)

Effects of Probiotics on Markers of Oxidative/Nitrosative Stress and Damage Associated with Inflammation in Non-communicable Diseases: A Systematic Review and Meta-analysis of Randomized Placebo-Controlled Trials - Natanny Swerts Silva; Cláudio Daniel Cerdeira; Tiago Marques dos Reis; Maria Rita Rodrigues (Probiotics and Antimicrobial Proteins, 2026)

Evaluation of the stability of concentrate feed stored in metallic silos under farm conditions in Brazil - Tiago Bordin; Elisangela Vilas Boas; Pedro Henrique Ferreira da Silva; Luciane Maria Colla; Fernando Pilotto; Laura Beatriz Rodrigues (Journal of Consumer Protection and Food Safety, 2026)
Maintaining the nutritional quality of stored concentrates is crucial for the health and productivity of dairy herds, particularly in tropical climates where high temperatures can accelerate feed degradation. This study aimed to monitor the effects of temperature and humidity variations on the quality of pelleted concentrate feed in steel silos under real-world Brazilian farm conditions during 28-day storage. Three 4-ton steel silos containing concentrate feed for lactating cows were evaluated on a dairy farm in southern Brazil. Internal and external temperature and humidity were recorded continuously. Samples were collected weekly (D0-D28). They underwent bromatological, physicochemical, and microbiological analyses (vitamins A and D3, fatty acids, total aerobic count, and mold/yeast counts). Despite extreme conditions (50 °C, 90% relative humidity) in the steel silos, microbial counts remained stable. However, vitamins A and D3 decreased significantly (233 ± 12 to 132 ± 13.08 µg/100 g dry matter (DM) and 1,577 ± 74 to 929 ± 295 IU/kg DM, respectively; 15–20% loss), while other nutrients remained stable. While metallic silos effectively preserve the quality of bulk feed in the short term, significant thermosensitive nutrient losses occur under tropical conditions. Farmers should align storage durations with seasonal climate patterns and consider protective technologies for vitamins. The findings highlight the need for comparative studies of storage methods and practical solutions tailored to tropical dairy systems, where nutrient preservation directly impacts milk production economics.

Seasonal biochemical fingerprints of outdoor cultivated Spirulina (Limnospira platensis) and Microchloropsis gaditana: insights into compositional and functional shifts - Diana Lopes; Ana S.P. Moreira; Tiago Conde; Andreia Ferreira; Kayane Oliveira; Alexandra Conde; Helena R. Rocha; Marta Coelho; Ana Gomes; Manuela Pintado; Ana Alexandra Ramos; Hugo Pereira; et al. (Algal Research, 2026)

Microplastic pollution in Brazil's coastal marine surface waters: The first macroregional baseline from the global south - Thiarlen Marinho da Luz; Rafaela Ribeiro de Brito; Raíssa de Oliveira Ferreira; Ariane Guimarães; Bárbara Beatriz da Silva Nunes; Aline Sueli de Lima Rodrigues; Abraão Tiago Batista Guimarães; Ítalo Nascimento Freitas; Stênio Gonçalves da Silva Matos; Élida Priscila Bogéa Carvalho; Juliana dos Santos Mendonça; Christine C. Gaylarde; et al. (Marine Pollution Bulletin, 2026)

In Silico, in vitro, and in vivo studies of a 2-substituted quinazolin-4(3H)-one in T-cell acute lymphoblastic leukemia - Giorgio Antoniolli; Gilberto Carlos Franchi Junior; Keli Lima; Rayssa de Mello Lopes; Euzebio Guimarães Barbosa; João Agostinho Machado-Neto; Carmen Silvia Passos Lima; Tiago Rodrigues; Fernando Coelho (Toxicology and Applied Pharmacology, 2026)

Microplastics in motion: Genotoxic and redox imbalance impacts of systemic exposure in a murine model - Wesley Rodrigues Soares; Thiarlen Marinho da Luz; Raíssa de Oliveira Ferreira; Letícia Paiva de Matos; Rafaela Ribeiro de Brito; Alex Gomes Rodrigues; Bruno da Cruz Pádua; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Guilherme Malafaia (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Invasive but valuable: exploring the lipidome of Rugulopteryx okamurae for biotechnological applications - Riccardo Trentin; Wadi Macquigneau; Tiago Braga; Isabella Moro; Maria João Rodrigues; Luísa Custódio (Journal of Applied Phycology, 2026)

Strategic environmental assessment—exploring connections between environmental and health issues - Thomas B. Fischer; Ben Cave; Shiu Fung Hung; Tiago Rodrigues; Birgitte Fischer-Bonde; Ainhoa Gonzalez (Environmental Management, 2026)
In this paper, how changes to environmental aspects considered in strategic environmental assessment (SEA) can affect human health is explored, based on a comprehensive and systematic literature review. Whilst health is a key aspect for consideration in SEA, how it should be approached has remained subject to discussion. There is agreement, though, that at a minimum, health impacts from bio-physical environmental changes need be assessed. What this means is elaborated on in this paper. Challenges to and opportunities for an effective consideration of health in SEA are briefly outlined.

An alternative approach to estimate mismanaged plastic waste at the sub-national scale - Tiago Balieiro Cetrulo; Letícia Stevanato Rodrigues; Camila Sasahara; Sylmara Lopes Francelino Gonçalves Dias; Natália Molina Cetrulo; Francisco Silva Pinto; Costas A. Velis; Melanie Vianna Alencar; Bianca Gabani Gimenez; Carla Isobel Elliff; Luis Américo Conti; Vitória Milanez Scrich; et al. (Marine Pollution Bulletin, 2026)

Seroprevalence of Dirofilaria immitis and assessment of systemic inflammatory indexes in apparently healthy dogs from coastal northeastern Brazil - Naianne Araújo Félix; Aldo Severino da Silva Neto; Emanueli Maria Freitas Rodrigues; Adam Leal-Lima; Diana Célia Sousa Nunes-Pinheiro; Tiago Cunha Ferreira (Topics in Companion Animal Medicine, 2026)

Incremental Gaussian Mixture Neural model for Geophysical inverse problems - Tiago Mazzutti; Mauro Roisenberg; Bruno B. Rodrigues (Computers & Geosciences, 2026)

Microplastic pollution across the Brazilian coastline: Evidence from the MICROMar project, the largest coastal survey in the Global South - Thiarlen Marinho da Luz; Rafaela Ribeiro de Brito; Raíssa de Oliveira Ferreira; Ariane Guimarães; Bárbara Beatriz da Silva Nunes; Aline Sueli de Lima Rodrigues; Abraão Tiago Batista Guimarães; Ítalo Nascimento Freitas; Stênio Gonçalves da Silva Matos; Élida Priscila Bogéa Carvalho; Juliana dos Santos Mendonça; Christine C. Gaylarde; et al. (Environmental Research, 2025)

Catastrophic wildfires in the Pantanal wetlands as catalysts for transformative change - Alexandre de Matos Martins Pereira; Geraldo Alves Damasceno-Junior; Renata Libonati; Liana O. Anderson; Allan Henrique de Almeida Souza; Bruno Henrique dos Santos Ferreira; Andre Valle Nunes; André Luiz Siqueira; Angelica Guerra; Angelo Cipriano Pacelli Rabelo; Arnaud L.J. Desbiez; Arthur Henrique Leite Falcette; et al. (Environmental Science & Policy, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Komagataella pastoris KM71H Attenuates Cognitive Deficits and Depressive-Like Behavior by the TLR4/NF-κB Signaling Pathway in an Aβ1-40-Induced AD-Like Mouse Model - Paloma T. Birmann; Giuliana Petiz Zugno; Airton Sinott; Rafael R. Rodrigues; Fabricio R. Conceição; Fernanda Severo Sabedra Sousa; Tiago Collares; Fabiana K. Seixas; Lucielli Savegnago (Molecular Neurobiology, 2025)

Comparative analysis of isoprostanoid profiles in Chlorella sorokiniana grown under autotrophic and heterotrophic conditions - Tiago Conde; Diana Lopes; Valérie Gros; Guillaume Reversat; Camille Oger; Jean-Marie Galano; Claire Vigor; Alexandre M.C. Rodrigues; Natacha Coelho; Helena Cardoso; M. Rosário Domingues; Thierry Durand (Algal Research, 2025)

Grassland soil carbon dynamics in southern Brazil under different management and edaphoclimatic conditions - Kelly Tamires Urbano Daboit; Letícia Sequinatto Rossi; Leonardo Souza Rodrigues; Marlise Nara Ciotta; Gustavo Eduardo Pereira; Carolina Inês Probst Alves; Aline Lima de Sena; Carlos Vieira; Cimélio Bayer; Beatriz Macedo Medeiros; Tiago Celso Baldissera (Agriculture, Ecosystems & Environment, 2025)

The evolution of tadpole shape: first insights into larval diversity of the Physalaemus deimaticus group with the description of two new forms (Anura, Leptodactylidae, Leiuperinae) - Raíla Brena Araújo; Iasodhara Rodrigues Freire; Filipe Augusto Cavalcanti do Nascimento; Tiago Leite Pezzuti (Zoologischer Anzeiger, 2025)

Chemical profile, cytoprotection study and anxiolytic potential of Lentinus edodes extracts - Matheus da Silva Campelo; Elison Breno de Alencar Dantas; Vitória Maria de Freitas Franco; Izabell Maria Martins Teixeira; Hilton César Rodrigues Magalhães; Guilherme Julião Zocolo; Sandra de Aguiar Soares; Alice Maria Costa Martins; Tiago Lima Sampaio; José Eduardo Ribeiro Honório Júnior; Maria Elenir Nobre Pinho Ribeiro (Food Research International, 2025)

Land–use change alters soil phosphorus fractions in tropical forests in southeastern Brazil - Matheus Severo de Souza Kulmann; Kauky Mc Lean de Faria Santos; Tiago Paula da Silva; Luiz Alberto da Silva Rodrigues Pinto; Emanuel José Gomes de Araújo; Mauro Valdir Schumacher; Marcos Gervasio Pereira (New Forests, 2025)

Cytotoxic activity of the crude venom from Odontomachus affinis ants is mediated by thiol oxidation and mitochondrial dysfunction - Jorge Luis Maria Ruiz; Vyctória dos Santos Ramos; Débora Cristina de Oliveira Gonçalves; Thamires Regine Corga da Silva Angelo; Priscila dos Santos Pazini; Ricardo José Soares Torquato; Wagner Alves de Souza Júdice; Antonio Miranda; Edgar Julian Paredes-Gamero; Maria Santina de Castro Morini; Tiago Rodrigues (Toxicon, 2025)

Protection and safety of aluminum hydroxide adjuvant and chimeric antigen containing predicted epitopes from bacteria murC gene in Aeromonas hydrophila fish infection - Jojo Silva Rodrigues; Maria Roméria da Silva; Camila Aparecida Martins; Laura Alves Zuanon; Karina Ventura Boechat Martins; Pedro Segantini Tótola; Jheneze Guimarães Pereira Rocha; Mariana Grôppo Parma; Isabel Samila Lima Castro; Tarciza Fernandes Nascimento; Allan Rodrigues Pires; Filipe Silveira Azevedo; et al. (Fish & Shellfish Immunology, 2025)

Growth performance, phosphorus balance, gut function and bacteriome of juvenile Amazonian tambaqui (Colossoma macropomum) fed plant-based diets supplemented with phytase and/or xylanase-β-glucanase - Cristiana Leonor da Silva Carneiro; Bárbara Santos; Larissa Pacheco Cassemiro Monteiro; Felipe Rodrigues Saturnino; Mateus Magalhães Olegário; Alessandro Sebastião Gomes Quadros; Maria Goretti Oliveira de Almeida; Ronald Kennedy Luz; Tiago Antônio de Oliveira Mendes; Filipe Castro; Wilson Massamitu Furuya; Ana Lúcia Salaro (Aquaculture, 2025)

Biochar Application to Recover Degraded Soils: Comparison of Different Biomass Sources Assessed by Soil Physical Quality and Maize Growth - Tiago da Costa Dantas Moniz; João Marcos Rodrigues dos Santos; Gilvanete da Silva Henrique; Francisco Luan Almeida Barbosa; João Ivo Rodrigues de Sousa; Ícaro Vasconcelos do Nascimento; Alexandre dos Santos Queiroz; Carlos Tadeu dos Santos Dias; Maria Vitória Ricarte Gonçalves; Mirian Cristina Gomes Costa; Helon Hébano de Freitas Sousa; Francisca Gleiciane da Silva; et al. (Journal of Soil Science and Plant Nutrition, 2025)

The tectonic basement in the inflection area between the Tucano Norte Sub-basin and Jatobá Basin (Northeastern Brazil) using aeromagnetic and gravimetric data - Nicolas Rodrigues Hispagnol; Juarez Lourenço; Andrés Reinaldo Rodriguez Papa; Tiago Rafael Gregory; Byanca Cristiane Cristo Junior Cardoso (Earth Science Informatics, 2025)

Biochemical biomarker profiles of different organs of Phrynops geoffroanus freshwater turtle (Testudines, Chelidae) reveal pollutant effects from an anthropized aquatic environment - Maria Isabel Afonso da Silva; Daína Lima; Larissa Paola Rodrigues Venancio; Tiago Lucena da Silva; Claudia Regina Bonini Domingos; Eduardo Alves de Almeida (Environmental Research, 2025)

COVID-19 pandemic exacerbated food insecurity in South American countries - Carlos Frederico A. Vasconcelos-Neto; Michelle Jacob; Daniel Tregidgo; Denis Valle; Hani R. El Bizri; Sávio Marcelino Gomes; Julia E. Fa; Thais Q. Morcatty; Frederico Ozanan Barros Monteiro; Alessandra Scofield; Alessandra Matte; Willandia A. Chaves; et al. (Food Security, 2025)
The COVID-19 pandemic triggered unparalleled political, economic, and social ramifications, exacerbating global food insecurity (FI). To understand the overall impact of the pandemic and how different socio-economic groups were affected, we assessed prevalence and severity of FI in a sample of 18,997 households across seven countries in South America. We employed the Food Insecurity Experience Scale developed by the FAO. Our results showed that pre-pandemic, 4.5% of the sampled population across the entire continent faced Moderate FI, while 0.6% experienced severe FI. During the pandemic, Moderate FI increased to 16.9% (+ 12.4%), and Severe FI to 2.7% (+ 2.1%). By country, pre-pandemic households in Venezuela had the highest prevalence of Moderate FI (9.7%), with Peru experiencing the highest Severe FI frequency (1.1%). Peru had the greatest rise in Moderate (+ 23.9%) and Severe FI (+ 4.6%) during the pandemic. Low-income households, defined as those earning < 2 minimum wages per month, were most susceptible to FI. Uruguayan low-income families exhibited the most significant rise (+ 40.4%) in Moderate FI, while those in Peru experienced an increase of + 9.1% in Severe FI. This study measures the profound and far-reaching impact of the COVID-19 pandemic on FI in South America. Our findings also emphasise the critical importance of implementing effective public policy interventions to improve resilience against future shocks. This would enable policymakers to develop targeted strategies that address the immediate challenges posed by pandemics as well as laying the groundwork for a more resilient and sustainable food security landscape in the region.

Exploring nutritional and bioactive properties of Maranta arundinacea L.: An unconventional food plant - Yasmine Fernandes Oliveira; Rodolfo Dantas Lima Junior; Jorge Luiz Souza Simão; Tiago Dias; Tânia Aparecida Pinto de Castro Ferreira; Maurício Vicente Cruz; Kátia Flávia Fernandes; Marco Aurélio Sperança; Fabiola Manhas Verbi Pereira; Edenir Rodrigues Pereira-Filho; Larissa Silva Costa; Patricia Santos Lopes; et al. (Food Research International, 2025)

Unlocking water management optimization: A data-driven exploration through bibliometric analysis - Tiago Silveira Gontijo; Gustavo de Souza Groppo; İhsan Erdem Kayral; Alexandre de Cássio Rodrigues (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Assessment of wood residue blends from the amazon region for decentralized energy recovery and decarbonization: Combustion kinetics, thermodynamics and potential emissions - Mayara Gabi Moreira; Pedro Paulo Oliveira Rodrigues; Lúcia Fernanda Alves Garcia; Giulia Cruz Lamas; José Luiz Franciso Alves; Jean Constantino Gomes da Silva; Tiago Jose Pires de Oliveira; Thiago de Paula Protásio; Edgar A. Silveira (Biomass and Bioenergy, 2025)

Biomass of South Brazilian highland grassland under management with burning and mowing: Characterization of vegetation and feedstock for energy - Taíse Mariano Rodrigues; Martha Andreia Brand; Tássio Dresch Rech; Tiago Celso Baldissera; Cassiano Eduardo Pinto; Fabio Cervo Garagorry; Alexsandro Bayestorff da Cunha; Polliana D'Angelo Rios; Rodrigo Figueiredo Terezo; Giovanna de Oliveira Souza; Lucas de Lima Ribeiro (Biomass and Bioenergy, 2025)

Genetic insights into non-additive effects in tetraploid potato breeding - Luciana Aparecida Miguel; Rafaela Pereira Carvalho; Roberto Henrique de Lima Ribeiro; Mayra Alejandra Rincón Rueda; Ivan David Briceño-Pinzón; Lucimara Cruz de Souza; Vinicius Samuel Martins; Leticia Novais Padua; José Airton Rodrigues Nunes; Pedro Crescêncio de Souza Carneiro; Mário Henrique Murad Leite Andrade; Márcio Fernando Ribeiro Resende; et al. (Euphytica, 2025)

Changes in the sap proteome of Eucalyptus grandis and Eucalyptus urophylla plants grown at elevated CO₂ atmosphere - Felipe Alexsander Rodrigues da Silva; Lucas Amoroso Lopes de Carvalho; Adriana Grandis; Marcos Silveira Buckeridge; Tiago Santana Balbuena (Brazilian Journal of Botany, 2025)

Development of a rapid X-ray fluorescence method for protein determination in soybean grains - Rachel Ferraz de Camargo; Tiago Rodrigues Tavares; Felipe Rodrigues dos Santos; Hudson Wallace Pereira de Carvalho (Food Chemistry, 2025)

Mercerized Microcrystalline Cellulose: A Game-Changer for Sustainable Chromium Removal from Tannery Effluents - Alex Rodrigues Gomes; Letícia Paiva de Matos; Abner Marcelino Silva; Abraão Tiago Batista Guimarães; Thiarlen Marinho da Luz; Rafaela Ribeiro de Brito; Aline Sueli de Lima Rodrigues; Juraci Alves de Oliveira; Mônica Cristina Teixeira; Ivandilson Pessoa Pinto de Menezes; Chinnasamy Ragavendran; Marimuthu Govindarajan; et al. (Water, Air, & Soil Pollution, 2025)

Efficacy of a formulation of chlorfenvinphos and dichlorvos on Rhipicephalus microplus in vivo test in Bahia, Brazil - Aline Kelly Araújo Costa Velame Ferreira; Wagner Carvalho e Silva Neto; Igor de Castro Oliveira; Maria Clara Bastos Rodrigues; Ângela Cristina de Oliveira Lima; Tiago Velame Ferreira; Carolina Carneiro de Matos; Ana Karina da Silva Cavalcante; Lorendane Millena de Carvalho; Wendell Marcelo de Souza Perinotto (Tropical Animal Health and Production, 2025)

Assessment of risk to human health associated with the consumption of contaminated groundwater in the Western Brazilian Amazon - Josilena de Jesus Laureano; Elisabete Lourdes do Nascimento; Caryne Ferreira Ramos; Daíse da Silva Lopes; Luiza Fernanda Silva Pavanello; Tiago de Oliveira Lima; Alan Gomes Mendonça; Ana Lúcia Denardin da Rosa; Walkimar Aleixo da Costa Junior; Maria Cristina N. do N. Recktenvald; Wanderley Rodrigues Bastos (Environmental Geochemistry and Health, 2025)

The microbiota playing “musical chairs” in a glacier retreat zone of maritime Antarctica - Tomás Gomes Reis Veloso; José Maria Rodrigues da Luz; Marliane de Cássia Soares da Silva; José João Lelis Leal Souza; Larissa Marcia Anastácio; Tiago Iglésias Machado; Mateus Ferreira de Santana; Carlos Ernesto Gonçalves Reynaud Schaefer; Maria Catarina Megumi Kasuya (Applied Soil Ecology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Dynamics of flubendiamide resistance in Chrysodeixis includens (Walker) (Lepidoptera: Noctuidae) - Leonardo Souza Rodrigues; Lucas Gabriel Mass; Kelly Tamires Urbano Daboit; Luan Tiago dos Santos Carbonari; Suzana Sibila Pegoraro; Cláudio Roberto Franco (Crop Protection, 2025)

Acoustic wave propagation in oil wells: A comparison between semi-analytical and finite element modeling approaches - Luis Paulo Brasil de Souza; Juan Andrés Santisteban Hidalgo; Tiago de Magalhães Correia; Isabel Giron Camerini; Guilherme Rezende Bessa Ferreira; Antônio de Souza Rodrigues; Alan Conci Kubrusly; Arthur Martins Barbosa Braga (Wave Motion, 2025)

Death-driven exposure: Necrotrophic transfer of polylactic acid and polystyrene microplastics alters biochemical architecture in the saprophagous insect Chrysomya megacephala - Ariane Guimarães; Raíssa Ferreira de Oliveira; Abraão Tiago Batista Guimarães; Rafaela Ribeiro de Brito; Aline Sueli de Lima Rodrigues; Letícia Paiva de Matos; Thiarlen Marinho da Luz; Guilherme Malafaia (NanoImpact, 2025)

Unraveling the lipidome of Pavlova gyrans, a natural reservoir of bioactive lipids for biotechnological applications - Tiago Conde; Diana Lopes; Marisa Pinho; Tânia Melo; Natacha Coelho; Alexandre M. C. Rodrigues; Hugo Pereira; Pedro Domingues; Rosário Domingues (Journal of Applied Phycology, 2025)

Effects of deforestation on multitaxa community similarity in the Brazilian Atlantic Forest - Daniel Maurenza; Renato Crouzeilles; Jayme Augusto Prevedello; Mauricio Almeida‐Gomes; Marina Schmoeler; Renata Pardini; Cristina Banks‐Leite; Marcus Vinicius Vieira; Jean Paul Metzger; Carlos Roberto Fonseca; Marina Zanin; Alex Fernando Mendes; et al. (Conservation Biology, 2025)
Habitat loss can lead to biotic homogenization (decrease in β diversity) or differentiation (increase in β diversity) of biological communities. However, it is unclear which of these ecological processes predominates in human‐modified landscapes. We used data on vertebrates, invertebrates, and plants to quantify β diversity based on species occurrence and abundance among communities in 1367 landscapes with varying amounts of habitat ( 60% of forest cover) throughout the Brazilian Atlantic Forest. Decreases in habitat amount below 30% led to increased compositional similarity of vertebrate and invertebrate communities, which may indicate a process of biotic homogenization throughout the Brazilian Atlantic Forest. No pattern was detected in plant communities. We found that habitat loss was associated with a deterministic increase in faunal community similarity, which is consistent with a selected subset of species being capable of thriving in human‐modified landscapes. The lack of pattern found in plants was consistent with known variation between taxa in community responses to habitat amount. Brazilian legislation requiring the preservation of 20% of Atlantic Forest native vegetation may be insufficient to prevent the biotic homogenization of faunal communities. Our results highlight the importance of preserving large amounts of habitat, providing source areas for the recolonization of deforested landscapes, and avoiding large‐scale impacts of homogenization of the Brazilian Atlantic Forest.

Retraction notice to “Potential ecotoxicity of substrate-enriched zinc oxide nanoparticles to Physalaemus cuvieri tadpoles” [Sci. Total Environ. 873 (2023) 162382] - Alex Rodrigues Gomes; Abraão Tiago Batista Guimarães; Letícia Paiva de Matos; Abner Marcelino Silva; Aline Sueli de Lima Rodrigues; Raíssa de Oliveira Ferreira; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Chinnasamy Ragavendran; Chinnaperumal Kamaraj; Fabiano Guimarães Silva; Guilherme Malafaia (Science of The Total Environment, 2025)

Retraction notice to “Exposure of adult zebrafish (Danio rerio) to SARS-CoV-2 at predicted environmentally relevant concentrations: Outspreading warns about ecotoxicological risks to freshwater fish” [Sci. Total Environ. 880 (2023) 163269] - Thiarlen Marinho da Luz; Abraão Tiago Batista Guimarães; Stênio Gonçalves da Silva Matos; Sindoval Silva de Souza; Alex Rodrigues Gomes; Aline Sueli de Lima Rodrigues; Edison Luiz Durigon; Ives Charlie-Silva; Ítalo Nascimento Freitas; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Abner Marcelino Silva; et al. (Science of The Total Environment, 2025)

Abiu-do-Mato (Pouteria caimito, Sapotaceae): A promising Amazonian fruit with rich chemical composition, antioxidant potential, and cytotoxic safety - Andreza Cavalcante de Oliveira; Josias Martins dos Anjos Cruz; Josiana Moreira Mar; Renilto Frota Corrêa; Jojo Silva Rodrigues; Tiago Antônio de Oliveira Mendes; Jaime Paiva Lopes Aguiar; Francisca das Chagas do Amaral Souza; Kidney de Oliveira Gomes Neves; Alan Diego Conceição Santos; Edgar Aparecido Sanches; Pedro Henrique Campelo; et al. (Food Research International, 2025)

Morphoanatomy, ontogeny and histochemistry of internal mucilage-secreting structures in the bracts and flowers of three genera of Bromeliaceae - Tiago Augusto Rodrigues Pereira; Eliza Louback; Vanessa de Carvalho Harthman; Hugo Humberto de Araújo; Renata Maria Strozi Alves Meira; Luzimar Campos da Silva (Flora, 2025)

Persistent Effects of Naturally Aged Polyethylene Terephthalate Microplastics on Physalaemus cuvieri Tadpoles: The Toxic Legacy Beyond Exposure - Rafaela Ribeiro de Brito; Raíssa de Oliveira Ferreira; Wesley Rodrigues Soares; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Thiarlen Marinho da Luz; Alex Rodrigues Gomes; Letícia Paiva de Matos; Guilherme Malafaia (Water, Air, & Soil Pollution, 2025)

Complex Interactions and Ecotoxicological Consequences of Tannery Effluents on Aquatic Life: Differential Responses in Scinax Fuscovarius Tadpoles and Poecilia Reticulata Fish - Alex Rodrigues Gomes; Letícia Paiva de Matos; Abner Marcelino Silva; Abraão Tiago Batista Guimarães; Thiarlen Marinho da Luz; Rafaela Ribeiro de Brito; Aline Sueli de Lima Rodrigues; Boniek Gontijo Vaz; Juraci Alves de Oliveira; Wesley Rodrigues Soares; Ivandilson Pessoa Pinto de Menezes; Guilherme Malafaia (Water, Air, & Soil Pollution, 2025)

Necroecological Trophic Transfer of Microplastics: Insights into the Ecotoxicity of Petroleum-Derived and Biodegradable Polymers - Ariane Guimarães; Abraão Tiago Batista Guimarães; Rafaela Ribeiro de Brito; Alex Rodrigues Gomes; Ítalo Nascimento Freitas; Aline Sueli de Lima Rodrigues; Omar Cruz Santiago; Thiarlen Marinho da Luz; Letícia Paiva de Matos; Raíssa Ferreira de Oliveira; Guilherme Malafaia (Archives of Environmental Contamination and Toxicology, 2025)

Beyond the virus: ecotoxicological and reproductive impacts of SARS-CoV-2 lysate protein in C57Bl/6j female mice - Bárbara Beatriz da Silva Nunes; Juliana dos Santos Mendonça; Letícia Paiva de Matos; Abraão Tiago Batista Guimarães; Wesley Rodrigues Soares; Aline Sueli de Lima Rodrigues; Marimuthu Govindarajan; Alex Rodrigues Gomes; Thiarlen Marinho da Luz; Guilherme Malafaia (Environmental Science and Pollution Research, 2025)

Do XRF local models have temporal stability for predicting plant-available nutrients in different years? A long-term study showing the effect of soil fertility management in a tropical field - Tiago Rodrigues Tavares; Budiman Minasny; Alex McBratney; José Paulo Molin; Gabriel Toledo Marques; Marcos Mantelli Ragagnin; Felipe Rodrigues dos Santos; Hudson Wallace Pereira de Carvalho; José Lavres (Soil and Tillage Research, 2025)

Measuring commitment in paws: Adaptation of the Investment Model Scale to the context of companion animals with a Portuguese sample - Tiago Rôxo Aguiar; Diniz Lopes; David L. Rodrigues (Journal of Veterinary Behavior, 2025)

Addressing climate change in Berlin's local land-use plans through strategic environmental assessment and knowledge brokering - Tiago Rodrigues; Gesa Geißler; Marcelo Montaño (Environmental Impact Assessment Review, 2025)

A short and fast scrotal heat stress modifies sperm sncRNA cargo without altering morpho-functional sperm features - Maíra Bianchi Rodrigues Alves; Helena Fabiana Reis de Almeida Saraiva; Luana Alves; Tiago Henrique Camara de Bem; Ana Beatriz Bossois Moura; Angélica Camargo dos Santos; Marcos Roberto Chiaratti; Luciano Andrade Silva; Juliano Coelho da Silveira; Felipe Perecin (Animal Reproduction Science, 2025)

Feeding ecology of a detritivorous fish in controlled flood pulse area in the Amazon revealed by stomach content and stable isotopes analyses - Izabella Cristina da Silva Penha; Antonio Augusto Jardim; Erival Gonçalves Prata; Lidia Brasil Seabra; Rafael Rodrigues Gusmão; Giovanna Teixeira Ferreira; Ana Flavia do Vale Neves Machado Costa; Tiago Magalhães da Silva Freitas; Luciano Fogaça de Assis Montag (Aquatic Sciences, 2025)

Retraction notice to “Green toxicology approach involving polylactic acid biomicroplastics and neotropical tadpoles: (Eco)toxicological safety or environmental hazard?” [Sci. Total Environ. 783(2021) 146994] - Guilherme Malafaia; Ítalo Freitas Nascimento; Fernanda Neves Estrela; Abrao Tiago Batista Guimares; Fabianne Ribeiro; Thiarlem Marinho da Luz; Aline Sueli de Lima Rodrigues (Science of The Total Environment, 2024)

Retraction notice to “Toxicity of polystyrene nanoplastics in Ctenopharyngodon idella juveniles: A genotoxic, mutagenic and cytotoxic perspective” [Sci. Total Environ. 752(2021) 141937] - Abrao Tiago Batista Guimares; Fernanda Neves Estrela; Paulo Sergio Pereira; Julya Emmanuela de Andrade Vieira; Aline Sueli de Lima Rodrigues; Fabiano Guimares Silva; Guilherme Malafaia (Science of The Total Environment, 2024)

Retraction notice to “Carbon nanofibers are bioaccumulated in Aphylla williamsoni (Odonata) larvae and cause REDOX imbalance and changes of acetylcholinesterase activity” [Sci. Total Environ. 756 (2021) 143991] - Mateus Flores Montalvão; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Guilherme Malafaia (Science of The Total Environment, 2024)

Retraction notice to “Toxicity of polystyrene nanoplastics in dragonfly larvae: An insight on how these pollutants can affect bentonic macroinvertebrates” [Sci. Total Environ. 752 (2021) 141936] - Abrao Tiago Batista Guimares; Aline Sueli de Lima Rodrigues; Paulo Srgio Pereira; Fabiano Guimares Silva; Guilherme Malafaia (Science of The Total Environment, 2024)

Retraction notice to “Cellulose microcrystalline: A promising ecofriendly approach to control Culex quinquefasciatus larvae” [STOTEN 901 (2023) 165952] - Sindoval Silva de Souza; Alex Rodrigues Gomes; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Letícia Paiva de Matos; Juliana dos Santos Mendonça; Thiarlen Marinho da Luz; Stênio Gonçalves da Silva Matos; M. Safiur Rahman; Chinnasamy Ragavendran; Sengottayan Senthil-Nathan; Ajay Guru; et al. (Science of The Total Environment, 2024)

Retraction notice to “Toxicity assessment of SARS-CoV-2-derived peptides in combination with a mix of pollutants on zebrafish adults: A perspective study of behavioral, biometric, mutagenic, and biochemical toxicity” [Sci. Total Environ. 858 Part 2 (2023) 159838] - Ítalo Nascimento Freitas; Amanda Vieira Dourado; Amanda Pereira da Costa Araújo; Sindoval Silva de Souza; Thiarlen Marinho da Luz; Abraão Tiago Batista Guimarães; Alex Rodrigues Gomes; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Andrés Hugo Arias; Davoodbasha Mubarak Ali; Chinnasamy Ragavendran; et al. (Science of The Total Environment, 2024)

Retraction notice to “Hazardous effects of road-side soils on the redox and cholinesterasic homeostasis of mound-building termite (Cornitermes cumulans)” [STOTEN 815 (2022) 152841] - Lucas Eduardo Moreira Abadia; Alex Rodrigues Gomes; Ítalo Nascimento Freitas; Abraão Tiago Batista Guimarães; Boniek Gontijo Vaz; Mohamed Ahmed Ibrahim Ahmed; Thiarlen Marinho da Luz; Aline Sueli de Lima Rodrigues; Guilherme Malafaia (Science of The Total Environment, 2024)

Retraction notice to “Short-term exposure of the mayfly larvae (Cloeon dipterum, Ephemeroptera: Baetidae) to SARS-COV-2-derived peptides and other emerging pollutants: A new threat for the aquatic environments” [Sci. Total Environ. 849 (2022) 157813] - Ítalo Nascimento Freitas; Amanda Vieira Dourado; Stênio Gonçalves da Silva Matos; Sindoval Silva de Souza; Thiarlen Marinho da Luz; Aline Sueli de Lima Rodrigues; Abraão Tiago Batista Guimarães; Nabisab Mujawar Mubarak; Md. Mostafizur Rahman; Andrés Hugo Arias; Guilherme Malafaia (Science of The Total Environment, 2024)

Wastewater treatment plants circular performance models evaluation: Portugal case-study - Carlos Rodrigues; Tiago A.E. Martins; Leonor Amaral (Science of The Total Environment, 2024)

Vibrational spectroscopic techniques and variable selection in Linear Discriminant Analysis to geographical origin discrimination of Jatropha mollissima sap - Caroline Lins Fernandes; Tiago Santos Silva; Caike Lobo Rodrigues de Lima; Isabel Cristina Vicente dos Santos; Djair Araújo Fialho; Marcus Vinicius Lia Fook; Paulo Henrique Gonçalves Dias Diniz; José Filipe Bacalhau Rodrigues; Simone da Silva Simões (Phytochemistry Letters, 2024)

Combining predictive distribution methods and life history to reduce geographic distribution shortfalls for two rocky Cerrado endemic leaf frogs - Ana Cecília Holler Del Prette; Rafael Félix de Magalhães; Priscila Lemes; Tiago Leite Pezzuti; Christine Strüssmann; Caroline Batistim Oswald; Jean Carlo Pedroso de Oliveira; Fabrício Rodrigues dos Santos; Reuber Albuquerque Brandão (Journal for Nature Conservation, 2024)

Active biodegradable film with garlic essential oil: From elaboration to cytotoxicity and preliminary assessment of antibiotic resistance in Staphylococcus aureus - Clara Suprani Marques; Tarsila Rodrigues Arruda; Marcus Tulio Cunha dos Santos Filho; Amanda Camilo Graciano; Kamilla Soares de Mendonça; Bianca Muniz Lacerda Ventura; Amanda Lelis de Souza; Taíla Veloso de Oliveira; Tiago Antônio de Oliveira Mendes; Nilda de Fátima Ferreira Soares (Food Control, 2024)

Mesoproterozoic depleted spinel peridotites metasomatized by high-K hydrous melt in the Patagonian back-arc - Aline Alves dos Santos; Tiago Jalowitzki; Fernanda Gervasoni; Maurizio Mazzucchelli; Tommaso Giovanardi; Manuel Enrique Schilling; Maria Isabel Varas-Reus; Yuji Orihashi; Rodrigo Freitas Rodrigues; Richard Walter Carlson; Georgina Marianela Rubiano Lorenzoni; Daiji Hirata; et al. (Chemical Geology, 2024)

Resource-efficiency of cyanobacterium production on Mars: Assessment and paths forward - Tiago P. Ramalho; Vincent Baumgartner; Nils Kunst; David Rodrigues; Emma Bohuon; Basile Leroy; Guillaume Pillot; Christiane Heinicke; Sven Kerzenmacher; Marc Avila; Cyprien Verseux (Algal Research, 2024)

Aqueous extract of Spirulina exerts neuroprotection in an experimental model of Alzheimer sporadic disease in mice induced by Streptozotocin - Juliete Tavares; Alfaete Vieira Oliveira; Tyciane de Souza Nascimento; Jessica Maria Pessoa Gomes; Ana Caroline Barros Parente; Jessica Rabelo Bezerra; Mac Dionys Rodrigues da Costa; Mayara Sandrielly Soares de Aguiar; Tiago Lima Sampaio; Francisco Arnaldo Viana Lima; Glauce Socorro de Barros Viana; Geanne Matos de Andrade (Metabolic Brain Disease, 2024)

In situ determination of soybean leaves nutritional status by portable X-ray fluorescence: An initial approach for data collection and predictive modelling - Thainara Rebelo da Silva; Eduardo de Almeida; Tiago Rodrigues Tavares; Fábio Luiz Melquiades; Murilo Mesquita Baesso; Rachel Ferraz de Camargo; Marcos Henrique Feresin Gomes; Hudson Wallace Pereira de Carvalho (Biosystems Engineering, 2024)

Evolution of land surface temperature, land use land cover and their relationship: A case study of Maceió, Brazil - Michelle Adelino Cerqueira; Ricardo Victor Rodrigues Barbosa; Tiago Peixoto da Silva Lôbo (Urban Climate, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Dissemination and characterization of Escherichia coli resistant to extended-cephalosporins in feedlot lambs: A two-year two-population study - Katia Suemi Gozi; Caroline Rodrigues da Silva; Marlon do Valle Barroso; Jessica Priscila Barboza; Juliana Regina Peiró; Jean-Yves Madec; Marisa Haenni; Luiz Claudio Nogueira Mendes; Mara Corrêa Lelles Nogueira; Tiago Casella (Comparative Immunology, Microbiology and Infectious Diseases, 2024)

Assessing the of carbon and nitrogen storage potential in Khaya spp. stands in Southeastern Brazil - Gabriel Soares Lopes Gomes; Marcos Vinicius Winckler Caldeira; Robert Gomes; Victor Braga Rodrigues Duarte; Dione Richer Momolli; Tiago de Oliveira Godinho; Sarah Ola Moreira; Paulo André Trazzi; Laio Silva Sobrinho; Angélica de Cássia Oliveira Carneiro; Mauro Valdir Schumacher (New Forests, 2024)

Multidrug-resistant Escherichia coli isolated from free-range chickens in the Caatinga biome - Débora Luise Canuto de Sousa; José Diniz de Souto Sobrinho; Bianca Lara Venâncio de Godoy; Domingos Andrade Neto; Giliel Rodrigues Leandro; Tiago Casella; Sérgio Santos de Azevedo; Carolina de Sousa Américo Batista Santos (Veterinary Research Communications, 2024)

Multi-environment clonal selection using ideotype-design derived from factor analytic linear mixed models: an application on Eucalyptus breeding - Lenin Pereira Barros; Tiago de Souza Marcal; Flavia Maria Avelar Goncalves; Jose Airton Rodrigues Nunes; Vinicius Quintao Carneiro; Thiago Tavares Botelho; Aurelio Mendes Aguiar; Jose Luis Lima; Donizete da Costa Dias (Euphytica, 2024)

Fine root production and decomposition of integrated plants under intensified farming systems in Brazil - Wanderlei Bieluczyk; Marisa de Cássia Piccolo; João Vitor Matos Gonçalves; Marcos Gervasio Pereira; George Rodrigues Lambais; Plínio Barbosa de Camargo; Tiago Rodrigues Tavares; Amandine Germon; Cristiam Bosi; Alberto Carlos de Campos Bernardi; José Ricardo Macedo Pezzopane; Maurício Roberto Cherubin; et al. (Rhizosphere, 2024)

Temporal evaluation of soil chemical quality using VNIR and XRF spectroscopies - Henrique Oldoni; Tiago Rodrigues Tavares; Thiago Luis Brasco; Maurício Roberto Cherubin; Hudson W. Pereira de Carvalho; Paulo S. Graziano Magalhães; Lucas Rios do Amaral (Soil and Tillage Research, 2024)

Effect of vitamin blend supplementation on the oxidative stability and beef quality parameters of Nellore cattle - Jenifer Maira Lima Ramos; Cris Luana de Castro Nunes; Henrique Franco Gonçalves; Victor Valerio de Carvalho; Guilherme de Souza Floriano Machado de Vasconcelos; Tiago Sabela Acedo; Dhones Rodrigues de Andrade; Erica Beatriz Schultz; Leandro Licursi de Oliveira; Sebastião de Campos Valadares Filho; Mario Luiz Chizzotti (Livestock Science, 2024)

How do replanted mangroves affect phosphorus dynamics in their soils? - Gabriela Rodrigues da Silva; Marcela Lopes Lázaro; Hermano Melo Queiroz; Amanda Duim Ferreira; Rut Amelia Díaz Ramos; Wilson Thadeu Valle Machado; Xosé L. Otero; Tiago Osório Ferreira; Gabriel Nuto Nóbrega (Journal of Environmental Management, 2024)

Changes in artisanal fishing as a driver of the shifting baseline syndrome: from the perspective of local ecological knowledge - Macelly Correia Medeiros; Anderson Silva Pinto; Erimágna de Morais Rodrigues; Tiago Almeida de Oliveira; José Valberto de Oliveira; Sérgio de Faria Lopes; José da Silva Mourão (Marine Policy, 2024)

Sulfamerazine degradation employing a novel Z-scheme TiO2/KNbO3/g-C3N4 photocatalyst under artificial sunlight: Insights on degradation mechanism and toxicity - Nicolas Perciani de Moraes; Tiago Moreira Bastos Campos; Gilmar Patrocínio Thim; Yu Lianqing; Robson da Silva Rocha; Renata Colombo; Liana Alvares Rodrigues; Marcos Roberto de Vasconcelos Lanza (Journal of Environmental Chemical Engineering, 2024)

Proximal sensors for modeling clay mineralogy and characterization of soil textural fractions developed from contrasting parent materials - Fernanda Magno Silva; Sérgio Henrique Godinho Silva; Renata Andrade; João Augusto Coblinski; Alberto Vasconcellos Inda; Gustavo Frosi; Suane de Souza Franco Lima; Michele Duarte de Menezes; Tiago Rodrigues Tavares; Luiz Roberto Guimarães Guilherme; David C. Weindorf; Nilton Curi (CATENA, 2024)

Are CAM bromeliad seedlings from Campo Rupestre more tolerant to heat than C3? - Alexandre Aparecido Duarte; Tiago Vilas-Boas; Andréa Rodrigues Marques; José Pires de Lemos-Filho (Theoretical and Experimental Plant Physiology, 2024)

Corrigendum to “Green toxicology approach involving polylactic acid biomicroplastics and neotropical tadpoles: (Eco)toxicological safety or environmental hazard?” [Science of The Total Environment, 783 (2021), 146,994] - Guilherme Malafaia; Ítalo Freitas Nascimento; Fernanda Neves Estrela; Abraão Tiago Batista Guimarães; Fabianne Ribeiro; Thiarlen Marinho da Luz; Aline Sueli de Lima Rodrigues (Science of The Total Environment, 2024)

Exposure to microcrystallized cellulose affects the health of tadpoles and sheds light on the threat these materials pose to amphibians - Sindoval Silva de Souza; Alex Rodrigues Gomes; Abraão Tiago Batista Guimarães; Letícia Paiva de Matos; Juliana dos Santos Mendonça; Thiarlen Marinho da Luz; Stênio Gonçalves da Silva Matos; Aline Sueli de Lima Rodrigues; Sengottayan Senthil-Nathan; Md Refat Jahan Rakib; Chinnaperumal Kamaraj; Thiago Lopes Rocha; et al. (Environmental Pollution, 2024)

Corrigendum to ‘Multiple endpoints of polylactic acid biomicroplastic toxicity in adult zebrafish (Danio rerio)’ [Chemosphere, 277 (2021), 130279] - Thales Quintão Chagas; Ítalo Nascimento Freitas; Mateus Flores Montalvão; Rafael Henrique Nóbrega; Monica Rodrigues Ferreira Machado; Ives Charlie-Silva; Amanda Pereira da Costa Araújo; Abraão Tiago Batista Guimarães; Tenilce Gabriela da Silva Alvarez; Guilherme Malafaia (Chemosphere, 2024)

Toxicity of carbon nanofibers in earthworms (Lumbricus terrestris) naturally infected with Monocystis sp. - Mateus Flores Montalvão; Alex Rodrigues Gomes; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Letícia Paiva de Matos; Juliana dos Santos Mendonça; Thiarlen Marinho da Luz; Stênio Gonçalves da Silva Matos; M. Safiur Rahman; Chinnasamy Ragavendran; Sengottayan Senthil-Nathan; Ajay Guru; et al. (Science of The Total Environment, 2024)

Organic selenium and tocopherol supplementation for multiparous sows without adiabatic cooling: Effects on performance, milk composition, and serum antioxidant enzymes - Tiago Silva Andrade; Pedro Henrique Watanabe; Ingrid Barbosa de Mendonça; Eloisa Helena Mendes Vieira; Gabriel Gobira de Alcântara Araújo; Deborah Marrocos Sampaio Vasconcelos; Bruno Alexander Nunes Silva; Ednardo Rodrigues Freitas (Animal Feed Science and Technology, 2024)

An improved reference genome and first organelle genomes of Quercus suber - Ana Usié; Octávio Serra; Pedro M. Barros; Pedro Barbosa; Célia Leão; Tiago Capote; Tânia Almeida; Leandra Rodrigues; Isabel Carrasquinho; Joana B. Guimarães; Diogo Mendoça; Filomena Nóbrega; et al. (Tree Genetics & Genomes, 2023)
Cork oak ( Quercus suber L.) is an ecologically and economically important evergreen tree species native to the Mediterranean region and widespread in southwest Europe and northwest Africa. An improved genome assembly of cork oak using a combination of Illumina and PacBio sequencing is presented in this study. The assembled genome contains 2351 scaffolds longer than 1000 bp, accounting for 765.7 Mbp of genome size, L90 of 755, and a N50 of 1.0 Mbp, with 40,131 annotated genes. The repetitive sequences constitute 53.6% of the genome. The genome sequences of chloroplast and mitochondrion were determined for the first time, with a genome size of 161,179 bp and 531,858 bp, respectively. Phylogenetic analysis based on complete chloroplast genome sequence showed that Q. suber is closely related to Quercus variabilis , two cork-producing species with commercial use. All data generated are available through the public databases, being ready to be used without restrictions. This study provides an improved nuclear genome assembly together with the organelle genomes of cork oak. These resources will be useful for further breeding strategies and conservation programs and for comparative genomic studies in oak species.

RETRACTED: Cellulose microcrystalline: A promising ecofriendly approach to control Culex quinquefasciatus larvae - Sindoval Silva de Souza; Alex Rodrigues Gomes; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Letícia Paiva de Matos; Juliana dos Santos Mendonça; Thiarlen Marinho da Luz; Stênio Gonçalves da Silva Matos; M. Safiur Rahman; Chinnasamy Ragavendran; Sengottayan Senthil-Nathan; Ajay Guru; et al. (Science of The Total Environment, 2023)

Methodological insights from unmanned system technologies in a rock quarry environment and geomining heritage site: coupling LiDAR-based mapping and GIS geovisualisation techniques - Ana Pires; André Dias; Pedro Silva; António Ferreira; Paulo Rodrigues; Tiago Santos; Alexandre Oliveira; Liliana Freitas; Alfredo Martins; José Almeida; Eduardo Silva; Helder I. Chaminé (Arabian Journal of Geosciences, 2023)

Non-invasive methods to quantify the carcass parameters of sheep: Interaction between thermal environment and residual feed intake - Gabriel Ravi Gama Fontes; Glayciane Costa Gois; Rafael Torres de Souza Rodrigues; David Ramos da Rocha; Tiago Santos Silva; Joanigo Fernando Simão; Nataline Silva Araújo; Silvia Helena Nogueira Turco; Flávio Barbosa Matias; José Gledyson da Silva; Bernardo José Marques Ferreira; Daniel Ribeiro Menezes; et al. (Journal of Thermal Biology, 2023)

Advancing plastic pollution hotspotting at the subnational level: Brazil as a case study in the Global South - Melanie Vianna Alencar; Bianca Gabani Gimenez; Camila Sasahara; Carla Isobel Elliff; Costas A. Velis; Letícia Stevanato Rodrigues; Luis Americo Conti; Sylmara Lopes Francelino Gonçalves-Dias; Tiago Balieiro Cetrulo; Vitória Milanez Scrich; Alexander Turra (Marine Pollution Bulletin, 2023)

Towards rapid analysis with XRF sensor for assessing soil fertility attributes: Effects of dwell time reduction - Tiago Rodrigues Tavares; José Paulo Molin; Elton Eduardo Novais Alves; Fábio Luiz Melquiades; Hudson Wallace Pereira de Carvalho; Abdul Mounem Mouazen (Soil and Tillage Research, 2023)

Cover plants can contribute on macronutrient accumulation in agroforestry systems during off-season - Everton Martins Arruda; Leonardo Santos Collier; Kevein Ruas Oliveira; Rilner Alves Flores; Leonardo Rodrigues Barros; Risely Ferraz-Almeida; Bruna Bandeira Nascimento; Marcos Paulo Santos; Tiago Camilo Duarte; Carlos Augusto Oliveira Andrade (Agroforestry Systems, 2023)

First report on the toxicity of SARS-CoV-2, alone and in combination with polyethylene microplastics in neotropical fish - Raíssa de Oliveira Ferreira; Abraão Tiago Batista Guimarães; Thiarlen Marinho da Luz; Aline Sueli de Lima Rodrigues; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Chinnasamy Ragavendran; Chinnaperumal Kamaraj; Ives Charlie-Silva; Edison Luiz Durigon; Helyson Lucas Bezerra Braz; Andrés Hugo Arias; et al. (Science of The Total Environment, 2023)

RETRACTED: Exposure of adult zebrafish (Danio rerio) to SARS-CoV-2 at predicted environmentally relevant concentrations: Outspreading warns about ecotoxicological risks to freshwater fish - Thiarlen Marinho da Luz; Abraão Tiago Batista Guimarães; Stênio Gonçalves da Silva Matos; Sindoval Silva de Souza; Alex Rodrigues Gomes; Aline Sueli de Lima Rodrigues; Edison Luiz Durigon; Ives Charlie-Silva; Ítalo Nascimento Freitas; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Abner Marcelino Silva; et al. (Science of The Total Environment, 2023)

Mantle metasomatism and refertilization beneath the SW margin of the São Francisco Craton, Brazil - Rodrigo Antonio de Freitas Rodrigues; Fernanda Gervasoni; Tiago Jalowitzki; Yannick Bussweiler; Jasper Berndt; Nilson Francisquini Botelho; Gláucia Queiroga; Marcos Paulo de Castro; Sebastiao William da Silva; Brunno Abilio Ciriaco; Ítalo Lopes de Oliveira; Stephan Klemme (Lithos, 2023)

Removal of Reactive Dyes from a Real Bichromatic Textile Effluent Employing Bio-Based Nanomagnetic Adsorbents - Kátia C. H. Bezerra; Jacqueline R. Nascimento; Tiago D. Martins; Sherlan G. Lemos; Elma N. V. M. Carrilho; Christiane de A. Rodrigues; Geórgia Labuto (Water, Air, & Soil Pollution, 2023)

Komagataella pastoris KM71H Mitigates Depressive-Like Phenotype, Preserving Intestinal Barrier Integrity and Modulating the Gut Microbiota in Mice - Paloma T. Birmann; Angela M. Casaril; Ana Paula Pesarico; Rafael R. Rodrigues; Fabricio R. Conceição; Fernanda Severo Sabedra Sousa; Tiago Collares; Fabiana K. Seixas; Lucielli Savegnago (Molecular Neurobiology, 2023)

Long-term exposure of zebrafish juveniles to carbon nanofibers at predicted environmentally relevant concentrations: Outspreading warns about ecotoxicological risks to freshwater fish - Mateus Flores Montalvão; Thales Quintão Chagas; Aline Sueli de Lima Rodrigues; Abraão Tiago Batista Guimarães; Guilherme Malafaia (Science of The Total Environment, 2023)

Plant-ZnO nanoparticles interaction: An approach to improve guinea grass (Panicum maximum) productivity and evaluation of the impacts of its ingestion by freshwater teleost fish - Alex Rodrigues Gomes; Letícia Paiva de Matos; Abraão Tiago Batista Guimarães; Ítalo Nascimento Freitas; Thiarlen Marinho da Luz; Abner Marcelino Silva; Stênio Gonçalves da Silva Matos; Aline Sueli de Lima Rodrigues; Raíssa de Oliveira Ferreira; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Chinnasamy Ragavendran; et al. (Journal of Hazardous Materials, 2023)

Soybean sorting based on protein content using X-ray fluorescence spectrometry - Rachel Ferraz de Camargo; Tiago Rodrigues Tavares; Nicolas Gustavo da Cruz da Silva; Eduardo de Almeida; Hudson Wallace Pereira de Carvalho (Food Chemistry, 2023)

Correction to: Characterization of Portuguese sown rainfed grasslands using remote sensing and machine learning - Tiago G. Morais; Marjan Jongen; Camila Tufik; Nuno R. Rodrigues; Ivo Gama; David Fangueiro; João Serrano; Susana Vieira; Tiago Domingos; Ricardo F. M. Teixeira (Precision Agriculture, 2023)

Does abscisic acid and xylem sap pH regulate stomatal responses in papaya plants submitted to partial root-zone drying? - Mara de Menezes de Assis Gomes; Luciane do Nascimento Siqueira; Tiago Massi Ferraz; Weverton Pereira Rodrigues; Fábio Afonso Mazzei Moura de Assis Figueiredo; Fabrício de Oliveira Reis; Eliemar Campostrini (Theoretical and Experimental Plant Physiology, 2023)

RETRACTED: Potential ecotoxicity of substrate-enriched zinc oxide nanoparticles to Physalaemus cuvieri tadpoles - Alex Rodrigues Gomes; Abraão Tiago Batista Guimarães; Letícia Paiva de Matos; Abner Marcelino Silva; Aline Sueli de Lima Rodrigues; Raíssa de Oliveira Ferreira; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Chinnasamy Ragavendran; Chinnaperumal Kamaraj; Fabiano Guimarães Silva; Guilherme Malafaia (Science of The Total Environment, 2023)

Multiple endpoints of polyethylene microplastics toxicity in vascular plants of freshwater ecosystems: A study involving Salvinia auriculata (Salviniaceae) - Alex Rodrigues Gomes; Ítalo Nascimento Freitas; Thiarlen Marinho da Luz; Abraão Tiago Batista Guimarães; Amanda Pereira da Costa Araújo; Chinnaperumal Kamaraj; Md. Mostafizur Rahman; Abu Reza Md. Towfiqul Islam; Andrés Hugo Arias; Fábia Barbosa da Silva; Sengodan Karthi; Omar Cruz-Santiago; et al. (Journal of Hazardous Materials, 2023)

Forage based diet as an alternative to a high concentrate diet for finishing young bulls - Effects on growth performance, greenhouse gas emissions and meat quality - José Santos-Silva; Susana P. Alves; Alexandra Francisco; Ana Paula Portugal; Maria Teresa Dentinho; João Almeida; José Leandro Regedor da Silva; Letícia Fialho; Liliana Cachucho; Eliana Jerónimo; Ana Barradas; António Rodrigues; et al. (Meat Science, 2023)

Phenotypic and genotypic characterization of antibiotic resistance of Salmonella Heidelberg in the south of Brazil - Luana Sielski Galvão Soares; Tiago Casella; Eric Kazuo Kawagoe; Vilmar Benetti Filho; Wellington Pine Omori; Mara Corrêa Lelles Nogueira; Glauber Wagner; Rafael Rodrigues de Oliveira; Sabine Rippel Stahlhofer; Fabienne Antunes Ferreira; Eduardo Cesar Tondo; Juliano De Dea Lindner (International Journal of Food Microbiology, 2023)

Pedogenesis on Jurassic formations in the Araripe Basin, northeastern Brazil: Weathering and parent material - Carlos Roberto Pinheiro Junior; Tiago Rodrigues Tavares; Marcos Gervasio Pereira; Sheila Aparecida Correia Furquim; Fabrício da Silva Terra; Lúcia Helena Cunha dos Anjos; José Alexandre Melo Demattê; Antônio Carlos de Azevedo; Fábio Soares de Oliveira (CATENA, 2023)

Disinformation permeates Castro's reply to Rajão et al. (2022) - Raoni Rajão; Antonio Donato Nobre; Evandro L.T.P. Cunha; Tiago Ribeiro Duarte; Camilla Marcolino; Britaldo S. Soares-Filho; Gerd Sparovek; Ricardo R. Rodrigues; Carlos Valera; Mercedes Bustamante; Carlos Nobre; Letícia Santos de Lima (Biological Conservation, 2023)

Unveiling the membrane bound dihydroorotate: Quinone oxidoreductase from Staphylococcus aureus - Filipe M. Sousa; Patrícia Pires; Andreia Barreto; Patrícia N. Refojo; Micael S. Silva; Pedro B. Fernandes; Ana P. Carapeto; Tiago T. Robalo; Mário S. Rodrigues; Mariana G. Pinho; Eurico J. Cabrita; Manuela M. Pereira (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2023)

Modeling covariance structures and optimizing Jatropha curcas breeding - Jeniffer Santana Pinto Coelho Evangelista; Marco Antônio Peixoto; Igor Ferreira Coelho; Filipe Manoel Ferreira; Tiago de Souza Marçal; Rodrigo Silva Alves; Saulo Fabricio da Silva Chaves; Erina Vitório Rodrigues; Bruno Gâlveas Laviola; Marcos Deon Vilela de Resende; Kaio Olimpio das Graças Dias; Leonardo Lopes Bhering (Tree Genetics & Genomes, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Effects of solid retention time and exposure mode to electric current on Remazol Brilliant Violet removal in an electro-membrane bioreactor - Tiago José Belli; João Paulo Bassin; Carlos Magno de Sousa Vidal; Maria Eliza Nagel Hassemer; Caroline Rodrigues; Flávio Rubens Lapolli (Environmental Science and Pollution Research, 2023)

Insights about levels and source appointment of petroleum hydrocarbons in Brazilian semi-arid coastal: baseline status assessment for ocean decade targets - Andre Henrique Barbosa de Oliveira; Gabrielle Melo Fernandes; Felipe Rodrigues dos Santos; Narelle Maia de Almeida; Tiago Rocha Nogueira; Diego de Quadros Melo; Laercio Lopes Martins; Rivelino Martins Cavalcante; Ronaldo Ferreira do Nascimento; Christopher Michael Reddy (Environmental Science and Pollution Research, 2023)

RETRACTED: Toxicity assessment of SARS-CoV-2-derived peptides in combination with a mix of pollutants on zebrafish adults: A perspective study of behavioral, biometric, mutagenic, and biochemical toxicity - Ítalo Nascimento Freitas; Amanda Vieira Dourado; Amanda Pereira da Costa Araújo; Sindoval Silva de Souza; Thiarlen Marinho da Luz; Abraão Tiago Batista Guimarães; Alex Rodrigues Gomes; Abu Reza Md. Towfiqul Islam; Md. Mostafizur Rahman; Andrés Hugo Arias; Davoodbasha Mubarak Ali; Chinnasamy Ragavendran; et al. (Science of The Total Environment, 2023)

Characterization of portuguese sown rainfed grasslands using remote sensing and machine learning - Tiago G. Morais; Marjan Jongen; Camila Tufik; Nuno R. Rodrigues; Ivo Gama; David Fangueiro; João Serrano; Susana Vieira; Tiago Domingos; Ricardo F.M. Teixeira (Precision Agriculture, 2023)

Synthesis of bis(ylidene) cyclohexanones and their antifungal activity against selected plant pathogenic fungi - Ueveton Pimentel da Silva; Bruno Wesley Ferreira; Bianca Lana de Sousa; Robert Weingart Barreto; Felipe Terra Martins; João Honorato de A. Neto; Boniek Gontijo Vaz; Rodolfo Rodrigues da Silva; Thaís Viana Fialho Martins; Tiago Antônio de Oliveira Mendes; Eduardo Vinícius Vieira Varejão (Molecular Diversity, 2023)

Endotoxin tolerance and low activation of TLR-4/NF-κB axis in monocytes of COVID-19 patients - Gilson P. Dorneles; Paula C. Teixeira; Alessandra Peres; Luiz Carlos Rodrigues Júnior; Simone Gonçalves da Fonseca; Marta Chagas Monteiro; Sarah Eller; Tiago F. Oliveira; Eliana M. Wendland; Pedro R. T. Romão (Journal of Molecular Medicine, 2023)

Exposure to polystyrene nanoplastics induces an anxiolytic-like effect, changes in antipredator defensive response, and DNA damage in Swiss mice - Abraão Tiago Batista Guimarães; Ítalo Nascimento Freitas; Nabisab Mujawar Mubarak; Md. Mostafizur Rahman; Fernando Postalli Rodrigues; Aline Sueli de Lima Rodrigues; Damià Barceló; Abu Reza Md. Towfiqul Islam; Guilherme Malafaia (Journal of Hazardous Materials, 2023)

Genomic analysis of Escherichia coli circulating in the Brazilian poultry sector - Caroline Rodrigues da Silva; Marlon do Valle Barroso; Katia Suemi Gozi; Herrison Fontana; Mara Corrêa Lelles Nogueira; Nilton Lincopan; Tiago Casella (Brazilian Journal of Microbiology, 2022)

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Colonization rather than fragmentation explains the geographical distribution and diversification of treefrogs endemic to Brazilian shield sky islands - Caroline Batistim Oswald; Priscila Lemes; Maria Tereza C. Thomé; Tiago Leite Pezzuti; Fabricio Rodrigues Santos; Paulo Christiano de Anchietta Garcia; Felipe Sá Fortes Leite; Rafael Félix de Magalhães (Journal of Biogeography, 2022)
Aim Geographical patterns of montane biodiversity worldwide are related to biotic and abiotic factors, such as historical climate dynamics and species dispersal capabilities, which affect the biota from population to community levels. Understanding of processes related to population diversification in extra‐Andean Neotropical mountains remains largely unknown. Here, we tested how colonization of new areas as opposed to fragmentation of geographical ranges influenced the distribution and diversification of frogs from Brazilian mountains. Location Espinhaço Range, the largest extra‐Andean mountain range in South America. Taxon Ledge treefrog Bokermannohyla saxicola . Methods We used multilocus DNA and morphometric data throughout the species' distribution to delimit lineages, infer phylogenetic relationships and estimate divergence times. We used ecological niche modelling ( ENM ) and approximate Bayesian computation ( ABC ) to reconstruct changes of geographical distribution and population sizes for testing alternative hypotheses of diversification concerning fragmentation and colonization. Results We found four evolutionary significant lineages that diverged from the Pliocene to the Early Pleistocene. All lineages were validated by DNA and morphometric data by independent and joint analyses. ENM showed that climatic fluctuations might have influenced the species' distribution, whereas ABC model selection further supports associated demographic changes. Taken together, a Pleistocene jump‐dispersal scenario best explains the diversification of the Bokermannohyla saxicola lineages. Main conclusions Endemism in the Espinhaço Range is usually explained by ancient diversification, associated with long‐term isolation of climatic stable areas following climate‐driven habitat fragmentation. Our results challenge this general view, indicating recent diversification, habitat expansion and colonization of new areas as important processes explaining the current distribution and genetic diversity of B. saxicola .

Carbapenem-resistant IMP-1-producing Pseudocitrobacter vendiensis emerging in a hemodialysis unit - Letícia Kellen de Andrade; Arturo Levican; Louise Cerdeira; Andressa Batista Zequini de Morais; Melissa Maia Braz; Evelin Rodrigues Martins; Tiago Casella; Quézia Moura; Bruna Fuga; Nilton Lincopan; Mara Corrêa Lelles Nogueira (Brazilian Journal of Microbiology, 2022)

Molecular Detection of Trypanosoma kaiowa in Tabanus triangulum (Diptera: Tabanidae) from the Coastal Plain of Rio Grande do Sul, Southern Brazil - Gratchela D. Rodrigues; Eduardo Blodorn; Ândrio Zafalon-Silva; William Domingues; Roberta Marques; Tiago K. Krolow; Gonzalo Greif; Vinicius F. Campos; Rodrigo F. Krüger (Acta Parasitologica, 2022)

Passion fruit seed cake in the feeding of meat quails: effects on performance, carcass characteristics, lipid stability of the meat, litter quality, and economic viability - Tiago Freitas Silva; Ednardo Rodrigues Freitas; Thalles Ribeiro Gomes; Rafael Carlos Nepomuceno; Otoniel Félix de Souza; Edibergue Oliveira dos Santos; Marcelle Craveiro Abreu de Melo; Paula Joyce Delmiro de Oliveira Lima (Tropical Animal Health and Production, 2022)

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

Better light spectral quality and thermal amplitude inside the greenhouse stimulate growth and improve acclimatization of in vitro–grown Cattleya warneri T. Moore - Luciene Souza Ferreira; Andressa Leal Generoso; Virginia Silva Carvalho; Fábio Afonso Mazzei Moura de Assis Figueiredo; Rafael Walter; Tiago Massi Ferraz; Jefferson Rangel da Silva; Geraldo de Amaral Gravina; Weverton Pereira Rodrigues; Wagner A. Vendrame; Eliemar Campostrini (In Vitro Cellular & Developmental Biology - Plant, 2021)

Identification and characterization of acid and alkaline phosphatases and protein phosphatases in L. catesbeianus tail during metamorphosis - Adriano Marques Gonçalves; Caroline Carla Santana; Luiz Flávio José Dos Santos; Rafael Rodrigues Colosio; Tiago Santana Balbuena; João Martins Pizauro (Biologia, 2021)

Leaf morphology of melon mediates feeding and oviposition preference, and immature survival of Liriomyza sativae (Blanchard) (Diptera: Agromyzidae) - Josielma Monteiro de Oliveira; Nívia da Silva Dias-Pini; José Wagner da Silva Melo; Wenner Vinicius Araújo Saraiva; Celli Rodrigues Muniz; Tiago Cardoso da Costa Lima; Valter Rodrigues Oliveira; Gabriela Priscila de Sousa Maciel (Phytoparasitica, 2021)

CO2 enrichment leads to altered cell wall composition in plants of Pfaffia glomerata (Spreng.) Pedersen (Amaranthaceae) - Eliza Louback; Diego Silva Batista; Tiago Augusto Rodrigues Pereira; Talita Cristina Mamedes-Rodrigues; Tatiane Dulcineia Silva; Sérgio Heitor Sousa Felipe; Diego Ismael Rocha; Douglas André Steinmacher; Wagner Campos Otoni (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Textile effluent treatment employing yeast biomass and a new nanomagnetic biocomposite - Jacqueline R. Nascimento; Kátia C.H. Bezerra; Tiago D. Martins; Elma N.V.M. Carrilho; Christiane de A. Rodrigues; Geórgia Labuto (Environmental Science and Pollution Research, 2021)

In vitro propagation of cambuci (Campomanesia phaea): An endangered exotic fruit and ornamental plant from Brazilian Atlantic Forest - Christian Aparecido Demétrio; Jessica Fernanda de Oliveira Jacob; Guilherme Bovi Ambrosano; Ênio Tiago de Oliveira; Paulo Hercílio Viegas Rodrigues (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Performance of broiler chicken submitted to a quantitative feed restriction program - Tiago Bordin; Fernando Pilotto; Daniela Pesenatto; Bruno Sebastião de Mendonça; Luciane Daroit; Laura Beatriz Rodrigues; Ezequiel Davi dos Santos; Elci Lotar Dickel (Tropical Animal Health and Production, 2021)

Selection underlies phenotypic divergence in the insular Azores woodpigeon - Pedro Andrade; Daniele Cataldo; Rémi Fontaine; Tiago M. Rodrigues; João Queirós; Verónica Neves; Amélia Fonseca; Miguel Carneiro; David Gonçalves (Zoologica Scripta, 2021)
The study of phenotypic evolution in island birds following colonization is a classic topic in island biogeography. However, few studies explicitly test for the role of selection in shaping trait evolution in these taxa. Here, we studied the Azores woodpigeon ( Columba palumbus azorica ) to investigate differences between island and mainland populations, between females and males, and interactions between geographical origin and sex, by using spectrophotometry to quantify plumage colour and linear measurements to examine external and skeletal morphology. We further tested if selection explains the observed patterns by comparing phenotypic differentiation to genome‐wide neutral differentiation. Our findings are consistent with several predictions of morphological evolution in island birds, namely differences in bill, flight and leg morphology and coloration differences between island and mainland birds. Interestingly, some plumage and morphological traits that differ between females and males respond differently according to geographical origin. Sexual dimorphism in colour saturation is more pronounced in the mainland, but this is driven by selection on female plumage coloration. Differences in flight morphology between females and males are also more pronounced in the mainland, possibly to accommodate contrasting pressures between migration and flight displays. Overall, our results suggest that phenotypic differentiation between mainland and island populations leading to divergent sexual dimorphism patterns can arise from selection acting on both females and males on traits that are likely under the influence of natural and sexual selection.

Undecane production by cold-adapted bacteria from Antarctica - Michel Rodrigo Zambrano Passarini; Tiago Rodrigues e Silva; Suzan Prado Fernandes Bernal; Nathália Luana Cecchet; Adilson Sartoratto; Marcela Boroski; Alysson Wagner Fernandes Duarte; Júlia Ronzella Ottoni; Luiz Henrique Rosa; Valéria Maia de Oliveira (Extremophiles, 2020)

Transparent polyethylene covering film in tropical grapevines does not alter photosynthesis, plant growth, fruit quality or yield - Luciana Venturotti Braun de Almeida; Weverton Pereira Rodrigues; Jefferson Rangel da Silva; Fábio Afonso Mazzei Moura de Assis Figueiredo; Bruna Côrrea da Silva de Deus; Katherine Fraga Ruas; Tiago Massi Ferraz; Amanda de Oliveira Martins; Kevin Lee Griffin; Ricardo Bressan-Smith; Eliemar Campostrini (Theoretical and Experimental Plant Physiology, 2020)

Oxidative Stress, Nutritional Disorders, and Gas Exchange in Lettuce Plants Subjected to Two Selenium Sources - Raphael Leone da Cruz Ferreira; Renato de Mello Prado; Jonas Pereira de Souza Junior; Priscila Lupino Gratão; Tiago Tezotto; Flávio José Rodrigues Cruz (Journal of Soil Science and Plant Nutrition, 2020)

Assessment and mitigation of seismic risk at the urban scale: an application to the historic city center of Leiria, Portugal - Anna Blyth; Beatrice Di Napoli; Francesco Parisse; Zahir Namourah; Elsa Anglade; Anna-Maria Giatreli; Hugo Rodrigues; Tiago Miguel Ferreira (Bulletin of Earthquake Engineering, 2020)

Physiological effects of overexpressed sigma factors on fermentative stress response of Zymomonas mobilis - Tiago Benoliel; Marciano Régis Rubini; Carolina de Souza Baptistello; Christiane Ribeiro Janner; Vanessa Rodrigues Vieira; Fernando Araripe Torres; Adrian Walmsley; Lidia Maria Pepe de Moraes (Brazilian Journal of Microbiology, 2020)

Anti-Sarcocystis Antibodies in Lambs Deprived of Colostrum - Camila Encarnação Minuzzi; Fernando de Souza Rodrigues; Camila Balconi Marques; Tiago Gallina; Thiago Cardoso dos Santos; Luiza Pires Portella; Patricia Bräunig; Alisson Rodrigues Döhler; Luis Antonio Sangioni; Fernanda Silveira Flores Vogel (Acta Parasitologica, 2020)

Correction to: Bridging the gap between will and action on climate change adaptation in large cities in Brazil - Gabriela Marques Di Giulio; Roger Rodrigues Torres; David M. Lapola; Ana Maria Bedran-Martins; Maria da Penha Vasconcellos; Diego Rafael Braga; Marcos Paulo Fuck; Yohanna Juk; Veruska Nogueira; Ana Carolina Penna; Tiago Jacaúna; Marcelo Fetz; et al. (Regional Environmental Change, 2019)

Bridging the gap between will and action on climate change adaptation in large cities in Brazil - Gabriela Marques Di Giulio; Roger Rodrigues Torres; David M. Lapola; Ana Maria Bedran-Martins; Maria da Penha Vasconcellos; Diego Rafael Braga; Marcos Paulo Fuck; Yohanna Juk; Veruska Nogueira; Ana Carolina Penna; Tiago Jacaúna; Marcelo Fetz; et al. (Regional Environmental Change, 2019)

Chemical Characterization and Biotechnological Applicability of Pigments Isolated from Antarctic Bacteria - Tiago R. Silva; Renata S. N. Tavares; Ramon Canela-Garayoa; Jordi Eras; Marili V. N. Rodrigues; Iramaia A. Neri-Numa; Glaucia M. Pastore; Luiz H. Rosa; José A. A. Schultz; Hosana M. Debonsi; Lorena R. G. Cordeiro; Valeria M. Oliveira (Marine Biotechnology, 2019)

Pigments in an iridescent bacterium, Cellulophaga fucicola, isolated from Antarctica - Tiago R. Silva; Ramon Canela-Garayoa; Jordi Eras; Marili V. N. Rodrigues; Fábio N. dos Santos; Marcos N. Eberlin; Iramaia A. Neri-Numa; Glaucia M. Pastore; Renata S. N. Tavares; Hosana M. Debonsi; Lorena R. G. Cordeiro; Luiz H. Rosa; et al. (Antonie van Leeuwenhoek, 2019)

Arbuscular mycorrhizae and absence of cluster roots in the Brazilian Proteaceae Roupala montana Aubl. - Kelly da Silva Coutinho Detmann; Tiago de Souza Leite; Ricardo Rodrigues de Oliveira Neto; Marina Neves Delgado; Vitor Paiva Alcoforado Rebello; Aristéa Alves Azevedo; Maria Catarina Megumi Kasuya; Marc-André Selosse; Andréa Miyasaka de Almeida (Symbiosis, 2019)

ATLANTIC EPIPHYTES : a data set of vascular and non‐vascular epiphyte plants and lichens from the Atlantic Forest - Flavio Nunes Ramos; Sara Ribeiro Mortara; Nathalia Monalisa‐Francisco; João Pedro Costa Elias; Luiz Menini Neto; Leandro Freitas; Rodrigo Kersten; André Márcio Amorim; Fernando Bittencourt Matos; André Felippe Nunes‐Freitas; Suzana Alcantara; Marcia Helena Nagahama Alexandre; et al. (Ecology, 2019)
Epiphytes are hyper‐diverse and one of the frequently undervalued life forms in plant surveys and biodiversity inventories. Epiphytes of the Atlantic Forest, one of the most endangered ecosystems in the world, have high endemism and radiated recently in the Pliocene. We aimed to (1) compile an extensive Atlantic Forest data set on vascular, non‐vascular plants (including hemiepiphytes), and lichen epiphyte species occurrence and abundance; (2) describe the epiphyte distribution in the Atlantic Forest, in order to indicate future sampling efforts. Our work presents the first epiphyte data set with information on abundance and occurrence of epiphyte phorophyte species. All data compiled here come from three main sources provided by the authors: published sources (comprising peer‐reviewed articles, books, and theses), unpublished data, and herbarium data. We compiled a data set composed of 2,095 species, from 89,270 holo/hemiepiphyte records, in the Atlantic Forest of Brazil, Argentina, Paraguay, and Uruguay, recorded from 1824 to early 2018. Most of the records were from qualitative data (occurrence only, 88%), well distributed throughout the Atlantic Forest. For quantitative records, the most common sampling method was individual trees (71%), followed by plot sampling (19%), and transect sampling (10%). Angiosperms (81%) were the most frequently registered group, and Bromeliaceae and Orchidaceae were the families with the greatest number of records (27,272 and 21,945, respectively). Ferns and Lycophytes presented fewer records than Angiosperms, and Polypodiaceae were the most recorded family, and more concentrated in the Southern and Southeastern regions. Data on non‐vascular plants and lichens were scarce, with a few disjunct records concentrated in the Northeastern region of the Atlantic Forest. For all non‐vascular plant records, Lejeuneaceae, a family of liverworts, was the most recorded family. We hope that our effort to organize scattered epiphyte data help advance the knowledge of epiphyte ecology, as well as our understanding of macroecological and biogeographical patterns in the Atlantic Forest. No copyright restrictions are associated with the data set. Please cite this Ecology Data Paper if the data are used in publication and teaching events.

No genetic differentiation, but less diversity, in the Iberian breeding population of the Eurasian Curlew (Numenius arquata) - Tiago M. Rodrigues; Pedro Andrade; María Vidal; Martin Boschert; David Gonçalves; Jesús Domínguez (Journal of Ornithology, 2019)

Influence of obstacle color on locomotor and gaze behaviors during obstacle avoidance in people with Parkinson’s disease - Tiago Penedo; Paula Fávaro Polastri; Sérgio Tosi Rodrigues; Lucas Simieli; André Macari Baptista; Gabriel Felipe Moretto; Luis Felipe Itikawa Imaizumi; Felipe Balistieri Santinelli; Fabio Augusto Barbieri (Experimental Brain Research, 2018)

The potential reproductive toxicity of tannery effluent to the estrous cycle and ovarian follicular dynamics of female Swiss mice - Raíssa de Oliveira Ferreira; Abraão Tiago Batista Guimarães; Thiago Lopes Rocha; Aline Sueli de Lima Rodrigues; Bruna de Oliveira Mendes; Carlos Mesak; Guilherme Malafaia (Environmental Science and Pollution Research, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Front Cover - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)

Functional diversity mediates macroecological variation in plant–hummingbird interaction networks - Pietro Kiyoshi Maruyama; Jesper Sonne; Jeferson Vizentin‐Bugoni; Ana M. Martín González; Thais B. Zanata; Stefan Abrahamczyk; Ruben Alarcón; Andréa C. Araujo; Francielle P. Araújo; Andrea C. Baquero; Edgar Chávez‐González; Aline G. Coelho; et al. (Global Ecology and Biogeography, 2018)
Aim Species interaction networks are known to vary in structure over large spatial scales. We investigated the hypothesis that environmental factors affect interaction network structure by influencing the functional diversity of ecological communities. Notably, we expect more functionally diverse communities to form interaction networks with a higher degree of niche partitioning. Location: Americas. Time period: Current. Major taxa studied: Hummingbirds and their nectar plants. Methods We used a large dataset comprising 74 quantitative plant–hummingbird interaction networks distributed across the Americas, along with morphological trait data for 158 hummingbird species. First, we used a model selection approach to evaluate associations between the environment (climate, topography and insularity), species richness and hummingbird functional diversity as predictors of network structure (niche partitioning, i.e., complementary specialization and modularity). Second, we used structural equation models (SEMs) to ask whether environmental predictors and species richness affect network structure directly and/or indirectly through their influence on hummingbird functional diversity. For a subset of 28 networks, we additionally evaluated whether plant functional diversity was associated with hummingbird functional diversity and network structure. Results Precipitation, insularity and plant richness, together with hummingbird functional diversity (specifically, functional dispersion), were consistently strong predictors of niche partitioning in plant–hummingbird networks. Moreover, SEMs showed that environmental predictors and plant richness affected network structure both directly and indirectly through their effects on hummingbird functional diversity. Plant functional diversity, however, was unrelated to hummingbird functional diversity and network structure. Main conclusions: We reveal the importance of hummingbird functional diversity for niche partitioning in plant–hummingbird interaction networks. The lack of support for similar effects for plant functional diversity potentially indicates that consumer functional diversity might be more important for structuring interaction networks than resource functional diversity. Changes in pollinator functional diversity are therefore likely to alter the structure of interaction networks and associated ecosystem functions.

Reactive oxygen species and other biochemical and morphological biomarkers in the gills and kidneys of the Neotropical freshwater fish, Prochilodus lineatus, exposed to titanium dioxide (TiO2) nanoparticles - Talita Laurie Lustosa do Carmo; Vinicius Cavicchioli Azevedo; Priscila Rodrigues de Siqueira; Tiago Dutra Galvão; Fabrício Aparecido dos Santos; Cláudia Bueno dos Reis Martinez; Carlos Roberto Appoloni; Marisa Narciso Fernandes (Environmental Science and Pollution Research, 2018)

Publisher Correction to: Bacteria from Antarctic environments: diversity and detection of antimicrobial, antiproliferative, and antiparasitic activities - Tiago R. Silva; Alysson W. F. Duarte; Michel R. Z. Passarini; Ana Lucia T. G. Ruiz; Caio Haddad Franco; Carolina Borsoi Moraes; Itamar Soares de Melo; Rodney A. Rodrigues; Fabiana Fantinatti-Garboggini; Valéria Maia Oliveira (Polar Biology, 2018)

Bacteria from Antarctic environments: diversity and detection of antimicrobial, antiproliferative, and antiparasitic activities - Tiago R. Silva; Alysson W. F. Duarte; Michel R. Z. Passarini; Ana Lucia T. G. Ruiz; Caio Haddad Franco; Carolina Borsoi Moraes; Itamar Soares de Melo; Rodney A. Rodrigues; Fabiana Fantinatti-Garboggini; Valéria Maia Oliveira (Polar Biology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Correction to: Histological liver chances in Swiss mice caused by tannery effluent - Letícia Martins Rabelo; Abraão Tiago Batista Guimarães; Joyce Moreira de Souza; Wellington Alves Mizael da Silva; Bruna de Oliveira Mendes; Raíssa de Oliveira Ferreira; Aline Sueli de Lima Rodrigues; Guilherme Malafaia (Environmental Science and Pollution Research, 2018)

Use of ultraviolet–visible spectrophotometry associated with artificial neural networks as an alternative for determining the water quality index - Edson Marcelino Alves; Ramon Juliano Rodrigues; Caroline dos Santos Corrêa; Tiago Fidemann; José Celso Rocha; José Leonel Lemos Buzzo; Pedro de Oliva Neto; Eutimio Gustavo Fernández Núñez (Environmental Monitoring and Assessment, 2018)

Neocosmocercella fisherae n. sp. (Nematoda: Cosmocercidae), a parasite of the large intestine of Phyllomedusa bicolor (Boddaert) (Anura: Phyllomedusidae) from the Brazilian Amazon - Ana Nunes dos Santos; Allan Rodrigo de Oliveira Rodrigues; Fábio José dos Santos Rocha; Jeannie Nascimento dos Santos; Cynthya Elizabeth González; Francisco Tiago de Vasconcelos Melo (Systematic Parasitology, 2018)

Methionine Administration in Pregnant Rats Causes Memory Deficit in the Offspring and Alters Ultrastructure in Brain Tissue - Bruna Martins Schweinberger; André Felipe Rodrigues; Tiago Marcon dos Santos; Francieli Rohden; Silvia Barbosa; Paula Rigon da Luz Soster; Wania Aparecida Partata; Maria Cristina Faccioni-Heuser; Angela T. S. Wyse (Neurotoxicity Research, 2018)

Histological liver chances in Swiss mice caused by tannery effluent - Letícia Martins Rabelo; Abraão Tiago Batista Guimarães; Joyce Moreira de Souza; Wellington Alves Mizael da Silva; Bruna de Oliveira Mendes; Raíssa de Oliveira Ferreira; Aline Sueli de Lima Rodrigues; Guilherme Malafaia (Environmental Science and Pollution Research, 2018)

Clusia hilariana and Eugenia uniflora as bioindicators of atmospheric pollutants emitted by an iron pelletizing factory in Brazil - Luzimar Campos da Silva; Talita Oliveira de Araújo; Advanio Inácio Siqueira-Silva; Tiago Augusto Rodrigues Pereira; Letícia Nalon Castro; Eduardo Chagas Silva; Marco Antonio Oliva; Aristéa Alves Azevedo (Environmental Science and Pollution Research, 2017)

Bursatella leachii from Mar Menor as a Source of Bioactive Molecules: Preliminary Evaluation of the Nutritional Profile, In Vitro Biological Activities, and Fatty Acids Contents - Tiago Braga; Maria João Rodrigues; Hugo Pereira; João Varela; Luísa Barreira; Mercedes González-Wangüemert; Luísa Custódio (Journal of Aquatic Food Product Technology, 2017)

Global patterns of interaction specialization in bird–flower networks - Thais B. Zanata; Bo Dalsgaard; Fernando C. Passos; Peter A. Cotton; James J. Roper; Pietro K. Maruyama; Erich Fischer; Matthias Schleuning; Ana M. Martín González; Jeferson Vizentin‐Bugoni; Donald C. Franklin; Stefan Abrahamczyk; et al. (Journal of Biogeography, 2017)
Aim Among the world's three major nectar‐feeding bird taxa, hummingbirds are the most phenotypically specialized for nectarivory, followed by sunbirds, while the honeyeaters are the least phenotypically specialized taxa. We tested whether this phenotypic specialization gradient is also found in the interaction patterns with their floral resources. Location Americas, Africa, Asia and Oceania/Australia. Methods We compiled interaction networks between birds and floral resources for 79 hummingbird, nine sunbird and 33 honeyeater communities. Interaction specialization was quantified through connectance ( C ), complementary specialization ( H 2 ′), binary ( Q B ) and weighted modularity ( Q ), with both observed and null‐model corrected values. We compared interaction specialization among the three types of bird–flower communities, both independently and while controlling for potential confounding variables, such as plant species richness, asymmetry, latitude, insularity, topography, sampling methods and intensity. Results Hummingbird–flower networks were more specialized than honeyeater–flower networks. Specifically, hummingbird–flower networks had a lower proportion of realized interactions (lower C ), decreased niche overlap (greater H 2 ′) and greater modularity (greater Q B ). However, we found no significant differences between hummingbird– and sunbird–flower networks, nor between sunbird– and honeyeater–flower networks. Main conclusions As expected, hummingbirds and their floral resources have greater interaction specialization than honeyeaters, possibly because of greater phenotypic specialization and greater floral resource richness in the New World. Interaction specialization in sunbird–flower communities was similar to both hummingbird–flower and honeyeater–flower communities. This may either be due to the relatively small number of sunbird–flower networks available, or because sunbird–flower communities share features of both hummingbird–flower communities (specialized floral shapes) and honeyeater–flower communities (fewer floral resources). These results suggest a link between interaction specialization and both phenotypic specialization and floral resource richness within bird–flower communities at a global scale.

A new species of Neocosmocercella Baker & Vaucher, 1983 (Nematoda: Cosmocercidae), a parasite of Phyllomedusa vaillantii Boulenger (Anura: Phyllomedusidae) in the Caxiuanã National Forest, eastern Amazon, Brazil - Ana Nunes dos Santos; Allan Rodrigo Oliveira Rodrigues; Jeannie Nascimento dos Santos; Cynthya Elizabeth González; Francisco Tiago de Vasconcelos Melo (Systematic Parasitology, 2017)

Life cycle thinking in Brazil: challenges and advances towards a more comprehensive practice - Danielle Maia de Souza; Tiago Braga; Maria Cléa Brito de Figueirêdo; Marília I. S. Folegatti Matsuura; Fernando Rodrigues Teixeira Dias; Cássia Maria Lie Ugaya (The International Journal of Life Cycle Assessment, 2017)

Inbred mice strain shows neurobehavioral changes when exposed to tannery effluent - Joyce Moreira de Souza; Wellington Alves Mizael da Silva; Bruna de Oliveira Mendes; Abraão Tiago Batista Guimarães; Aline Sueli de Lima Rodrigues; Mateus Flores Montalvão; Dieferson da Costa Estrela; Anderson Rodrigo da Silva; Guilherme Malafaia (Environmental Science and Pollution Research, 2017)

Improving Heat Transfer at the Bottom of Vials for Consistent Freeze Drying with Unidirectional Structured Ice - Mónica Rosa; João M. Tiago; Satish K. Singh; Vítor Geraldes; Miguel A. Rodrigues (AAPS PharmSciTech, 2016)

Thioridazine inhibits gene expression control of the cell wall signaling pathway (CWI) in the human pathogenic fungus Paracoccidioides brasiliensis - Daniela Leite Jabes; Ana Claudia de Freitas Oliveira; Valquíria Campos Alencar; Fabiano Bezerra Menegidio; Débora Liliane Souza Reno; Daiene Souza Santos; David Aciole Barbosa; Renata Ozelami Vilas Boas; Rodrigo Luiz de Oliveira Rodrigues Cunha; Tiago Rodrigues; Regina Costa de Oliveira; Luiz R. Nunes (Molecular Genetics and Genomics, 2016)

Binding of phenothiazines into allosteric hydrophobic pocket of human thioredoxin 1 - Eric Allison Philot; David da Mata Lopes; Aryane Tofanello de Souza; Antônio Sérgio Kimus Braz; Iseli Lourenço Nantes; Tiago Rodrigues; David Perahia; Maria A. Miteva; Luis Paulo Barbour Scott (European Biophysics Journal, 2016)

Myelin Lipids Inhibit Axon Regeneration Following Spinal Cord Injury: a Novel Perspective for Therapy - Fernando M. Mar; Tiago F. da Silva; Marlene M. Morgado; Lorena G. Rodrigues; Daniel Rodrigues; Marta I. L. Pereira; Ana Marques; Vera F. Sousa; João Coentro; Clara Sá-Miranda; Mónica M. Sousa; Pedro Brites (Molecular Neurobiology, 2016)

Energy and protein requirements of non-descript breed hair lambs of different sex classes in the semiarid region of Brazil - Rafael Torres de Souza Rodrigues; Mario Luiz Chizzotti; Samara Rodrigues Martins; Ivonete Ferreira da Silva; Mário Adriano Ávila Queiroz; Tiago Santos Silva; Karina Costa Busato; Aderbal Marcos de Azevêdo Silva (Tropical Animal Health and Production, 2016)

Identification of protein markers for bioactivity in marine actinomycetes: a proteomic analysis - Sousa Joana; Dias Tiago; Rodrigues Sara; Santos Sanches Ilda; Gaudêncio Susana; Almeida M. Gabriela (Frontiers in Marine Science, 2016)

Relationships between sap-flow measurements, whole-canopy transpiration and reference evapotranspiration in field-grown papaya (Carica papaya L.) - Tiago Massi Ferraz; Alena Torres Netto; Fabrício De Oliveira Reis; Anderson Lopes Peçanha; Elias Fernandes De Sousa; José Altino Machado Filho; Weverton Pereira Rodrigues; David Michael Glenn; Eliemar Campostrini (Theoretical and Experimental Plant Physiology, 2015)

Cadmium stress antioxidant responses and root-to-shoot communication in grafted tomato plants - Priscila Lupino Gratão; Carolina Cristina Monteiro; Tiago Tezotto; Rogério Falleiros Carvalho; Letícia Rodrigues Alves; Leila Priscila Peters; Ricardo Antunes Azevedo (BioMetals, 2015)

Indirect methods for predicting body composition of Boer crossbreds and indigenous goats from the Brazilian semiarid - Tiago Santos Silva; Mario Luiz Chizzotti; Karina Costa Busato; Rafael Torres de Souza Rodrigues; Ivonete Ferreira da Silva; Mário Adriano Ávila Queiroz (Tropical Animal Health and Production, 2015)

Nitrogen metabolism in coffee plants in response to nitrogen supply by fertigation - Ana Paula Neto; José Laércio Favarin; André Rodrigues dos Reis; Tiago Tezotto; Rodrigo Estevam Munhoz de Almeida; José Lavres Junior; Luiz Antonio Gallo (Theoretical and Experimental Plant Physiology, 2015)

New Thermoresistant Polymorph from CO2 Recrystallization of Minocycline Hydrochloride - Miguel A. Rodrigues; João M. Tiago; Luis Padrela; Henrique A. Matos; Teresa G. Nunes; Lídia Pinheiro; António J. Almeida; Edmundo Gomes de Azevedo (Pharmaceutical Research, 2014)

Effects of fluconazole on Candida glabrata biofilms and its relationship with ABC transporter gene expression - Elza Fonseca; Sónia Silva; Célia Fortuna Rodrigues; Carlos Tiago Alves; Joana Azeredo; Mariana Henriques (Biofouling, 2014)

Carcass and non-carcass component yields of crossbred Boer and Brazilian semiarid indigenous goats subjected to different feeding levels - Samara Rodrigues Martins; Mario Luiz Chizzotti; Sandra Mari Yamamoto; Rafael Torres de Souza Rodrigues; Karina Costa Busato; Tiago Santos Silva (Tropical Animal Health and Production, 2014)

Methane emission of Santa Inês sheep fed cottonseed by-products containing different levels of gossypol - Paulo de Mello Tavares Lima; Pedro Batelli Oliveira; Aline Campeche; Guilherme Dias Moreira; Tiago do Prado Paim; Concepta McManus; Adibe Luiz Abdalla; Angela Maria Morais Dantas; Jurandir Rodrigues de Souza; Helder Louvandini (Tropical Animal Health and Production, 2014)

Optimizing sealed transports of small ornamental fish - Esteves Da Silva Rui; Morais Hugo; Reis Tiago; Vasco-Rodrigues Nuno; Correia João (Frontiers in Marine Science, 2014)

Marine actinomycetes from Madeira Archipelago preliminary taxonomic studies - Rodrigues Sara; Dias Tiago; Pereira Florbela; Santos Sanches Ilda; Gaudêncio Susana (Frontiers in Marine Science, 2014)

Metabolic and cellular alterations induced by diesel oil in Hypnea musciformis (Wulfen) J. V. Lamour. (Gigartinales, Rhodophyta) - Fernanda Ramlov; Tiago José Griebeler Carvalho; Éder Carlos Schmidt; Cintia Dalcuche Leal Martins; Marianne Gabi Kreusch; Eva Regina de Oliveira Rodrigues; Cláudia Marlene Bauer; Zenilda Laurita Bouzon; Paulo Antunes Horta; Marcelo Maraschin (Journal of Applied Phycology, 2013)

Isolation and characterization of rice (Oryza sativa L.) E3-ubiquitin ligase OsHOS1 gene in the modulation of cold stress response - Tiago Lourenço; Helena Sapeta; Duarte D. Figueiredo; Mafalda Rodrigues; André Cordeiro; Isabel A. Abreu; Nelson J. M. Saibo; M. Margarida Oliveira (Plant Molecular Biology, 2013)

Pharmacological demonstration of the differential involvement of protein kinase C isoforms in short- and long-term memory formation and retrieval of one-trial avoidance in rats - Monica R. M. Vianna; Daniela M. Barros; Tiago Silva; Humberto Choi; Cristina Madche; Cleverson Rodrigues; Jorge H. Medina; I. Izquierdo (Psychopharmacology, 2000)